Polyethylene composition

By controlling the resin temperature difference and the curve characteristics of cross-grade chromatography during the processing of the polyethylene composition, the problem of difficulty in taking into account the strength, fuse and processability of the polyethylene composition in the processing of the membrane is solved, and excellent mechanical properties and processing properties are achieved.

CN116444881BActive Publication Date: 2025-05-02ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310472973.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-07-28
Filing Date
2018-07-24
Publication Date
2025-05-02
Estimated Expiration
2038-07-24

AI Technical Summary

Technical Problem

When the existing polyethylene composition is processed as a diaphragm, it is difficult to take into account excellent strength, fuse performance and slit processability.

Method used

By heating and kneading the polyethylene composition with the solvent, the difference between the resin temperature of the maximum torque peak and the resin temperature of the second largest peak is below 25°C, and the elution temperature-accumulative elution amount curve and elution temperature-elution amount curve are adjusted by the temperature-raising elution grading technology of cross-classification chromatography to ensure that the swelling and melting process of the polyethylene is completed within the specified temperature difference.

Benefits of technology

When processing as a diaphragm, the polyethylene composition has excellent strength, fuse performance and slit processability, and solves the problem that both strength and processability are difficult to take into account in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116444881B_ABST
    Figure CN116444881B_ABST
Patent Text Reader

Abstract

The present invention relates to a polyethylene composition. The present invention relates to a polyethylene composition having the following characteristics (A) and (B). (A) In the elution temperature - cumulative elution amount curve obtained by measuring the elution amount per 1 °C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50 °C to 98 °C is 50% by mass or more and less than 80% by mass. (B) Among the elution components recovered per 1 °C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), at a temperature of 85 °C or higher and less than 105 °C, there is at least one elution component having a weight average molecular weight (M w ) of 200,000 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application date of July 24, 2018 and application number 201880047014.5. Technical Field

[0002] The present invention relates to polyethylene compositions. Background Art

[0003] Polyethylene is used for various purposes such as sheets, films, and molded bodies, and the raw material of battery separators is also one of its important uses. The separator is a porous membrane used for the main purpose of separating the positive electrode and the negative electrode inside the battery and allowing only ions to pass through. As other purposes, the strength for ensuring the strength of the battery, the shutdown (hereinafter also referred to as "fuse") function for preventing the danger of runaway battery reaction when the temperature inside the battery is high, etc. can be listed. Moreover, it is required to improve these characteristics at the same time.

[0004] Compared with the general polyethylene used in sheets, films, molded bodies, etc., polyethylene as a raw material for diaphragms is generally a polyethylene with a higher molecular weight and a high density, which is commercialized in the form of a powder. The reason why polyethylene as a raw material for diaphragms has a high molecular weight and a high density is to ensure the strength of the diaphragm. The reason why polyethylene as a raw material for diaphragms is in a powdered form is that it is difficult to granulate due to its high molecular weight and poor processability, and the powdered form is more excellent in processability.

[0005] In order to obtain excellent diaphragms, a lot of research and development has been carried out in the past. One of the topics is the control of thermal shrinkage during the film forming process. Usually, the manufacturing process of microporous membranes and the like includes a stretching process. Moreover, usually, after the stretching process, in order to suppress the thermal shrinkage after stretching and the thermal shrinkage in the use environment, an annealing (hereinafter also referred to as "heat setting") process is carried out to relax the molecular orientation. In the heat setting process, the molecular orientation is relaxed by the molecular movement of the component that is easy to move molecules at low temperatures (hereinafter also referred to as "amorphous component"). However, high-density polyethylene with high crystallinity has a small proportion of amorphous components, and sometimes the relaxation of molecular orientation is insufficient, and there is a problem that the thickness of the microporous membrane is unstable due to thermal shrinkage and the like.

[0006] As a method for solving this problem, a method is known in which the average molecular weight and molecular weight distribution of polyethylene are appropriately adjusted to ensure appropriate molecular mobility at low temperatures and to efficiently perform an annealing step (for example, see Patent Document 1).

[0007] In addition, when the average molecular weight of polyethylene is increased in order to improve the strength of the diaphragm, the relationship of the trade-off of its processability variation is also listed as one of the main problems. In order to solve this problem, the following method is known: by appropriately adjusting the average molecular weight and molecular weight distribution of polyethylene, the molded body is given excellent mechanical strength, and excellent solubility or meltability is ensured (for example, see patent document 2). In addition, in order to solve the same problem, the following method is also known: control the processing conditions (amount of solvent used, mixing temperature, mixing torque, etc.) of polyethylene powder (for example, see patent document 3).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 2014-118515

[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 2014-118535

[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 2010-235926 Summary of the invention

[0013] Problems to be solved by the invention

[0014] The inventions of Patent Documents 1 to 3 are inventions that are completed with the viewpoint of ensuring the strength of the film or controlling thermal shrinkage, but no research has been conducted to further consider the fusing function. Moreover, the inventions of Patent Documents 1 to 3 use polyethylene with high crystallinity, so the fusing function at low temperatures is insufficient. In addition, the inventions of Patent Documents 1 to 3 also have the following problems: due to its high molecular weight, the fluidity of polyethylene is extremely poor, and it takes a long time from the start to the end of fusing.

[0015] Therefore, an object of the present invention is to provide a polyethylene composition which can impart excellent strength and fuse performance when processed into a separator and has excellent slit processability.

[0016] Means used to solve problems

[0017] The present inventors have conducted intensive studies to solve the above problems and have found that when a polyethylene composition and a solvent are heated and kneaded together, when the difference between the resin temperature of the maximum torque peak observed and the resin temperature of the second largest peak is less than a predetermined temperature difference, that is, when the swelling and melting process of the polyethylene during kneading is completed at less than the predetermined temperature difference, and when the amount of the eluted component at 98°C in the elution temperature-cumulative elution amount curve obtained by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC) is within a specific range, and when the elution temperature-cumulative elution amount curve obtained by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC) has at least one weight average molecular weight (M) within a specific temperature range. w ) is an elution component of 200,000 or more, the above-mentioned problems can be solved, thereby completing the present invention.

[0018] That is, the present invention relates to the following contents. [1]

[0020] A polyethylene composition, wherein the polyethylene composition has the following characteristics (A) and (B):

[0021] (A) In an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 50% by mass or more and less than 80% by mass.

[0022] (B) in the fractions recovered at 1°C by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC), at least one weight average molecular weight (M) at a temperature of 85°C or more and less than 105°C w ) is an elution component of more than 200,000. [2]

[0024] The polyethylene composition according to [1], wherein when sieved using a sieve having a mesh size of 300 μm based on JIS Z 8815, no component remains on the sieve. [3]

[0026] The polyethylene composition according to [1] or [2], wherein the chlorine content of the polyethylene composition is 50 mass ppm or less. [4]

[0028] The polyethylene composition according to any one of [1] to [3], wherein the content of the additive for imparting fluidity in the polyethylene composition is 5000 ppm by mass or less. [5]

[0030] A polyethylene composition as described in any one of [1] to [4], wherein, in an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 94°C is less than 40% by mass. [6]

[0032] A polyethylene composition as described in any one of [1] to [5], wherein, in an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 94°C is 10% by mass or more. [7]

[0034] The polyethylene composition according to any one of [1] to [6], which has three or more peaks in an elution temperature-elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC). [8]

[0036] The polyethylene composition according to any one of [1] to [7], wherein

[0037] The polyethylene composition contains polyethylene powder,

[0038] When the polyethylene powder is sieved using sieves having mesh sizes of 53 μm, 75 μm, 106 μm, 150 μm, 212 μm, and 300 μm based on JIS Z 8815 and classified into each category,

[0039] The weight average molecular weight M1 of the coarsest powder type, the weight average molecular weight M2 of the largest proportion type, and the weight average molecular weight M3 of the finest powder type satisfy the relationship of the following formula 1.

[0040] 0.8≤M1 / M2≤1.2 and 0.8≤M3 / M2≤1.2 Formula 1 [9]

[0042] A polyethylene composition as described in any one of [1] to [8], wherein 24 g of liquid paraffin having an average molecular weight of 450 or more and less than 550 is kneaded for 10 minutes at a set temperature of 114°C and a rotation speed of 5 rpm using a small mixing extruder (Toyo Seiki Co., Ltd. product "Main Model 4C150", mixer model: R-60), then 16 g of the above polyethylene composition and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane are added, the rotation speed is set to 30 rpm and kneaded for 3 minutes, and then kneaded under the condition of raising the set temperature from 114°C to 163°C over 6 minutes, and in the torque curve obtained at this time, the difference between the resin temperature when the peak with the largest torque is detected and the resin temperature when the peak with the second largest torque is detected is less than 25°C.

[0043] Effects of the Invention

[0044] According to the present invention, it is possible to provide a polyethylene composition which can impart excellent strength and fuse performance when processed into a separator and has good slit processability. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The graph shows the elution temperature-cumulative elution amount curve obtained by cross fractionation chromatography (CFC) measurement.

[0046] Figure 2 The graph shows the elution temperature-elution amount curve obtained by cross fractionation chromatography (CFC) measurement. DETAILED DESCRIPTION

[0047] Hereinafter, a mode for implementing the present invention (hereinafter referred to as "this embodiment") will be described in detail. It should be noted that the present invention is not limited to the following this embodiment, and can be implemented with various modifications within the scope of the gist thereof.

[0048] In this specification, the term "melting performance" refers to a performance that allows melting even at low temperatures when processed into a separator, for example, and that the melting speed is sufficiently high.

[0049] [Polyethylene composition]

[0050] The polyethylene composition of the present embodiment has the following characteristics (A) and (B). The polyethylene composition of the present embodiment has the following characteristics (A) and (B), and can impart excellent strength and fusing performance when processed into a diaphragm. In addition, in the slit processing for adjusting the width of the film, it is possible to fully suppress the generation of undulations, burrs, etc. in the cross section of the film, so that the slit processability is excellent.

[0051] (A) In an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 50% by mass or more and less than 80% by mass.

[0052] (B) in the fractions recovered at 1°C by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC), at least one weight average molecular weight (M) at a temperature of 85°C or more and less than 105°C w ) is an elution component of more than 200,000.

[0053] The polyethylene composition of the present embodiment is in a powdery form, for example. In the following description, when in a powdery form, it may be referred to as "polyethylene powder".

[0054] The polyethylene composition of the present embodiment includes an ethylene polymer (hereinafter, sometimes referred to as "polyethylene"). As for the ethylene polymer, ethylene homopolymers and / or copolymers of ethylene and other comonomers copolymerizable with ethylene (for example, binary or ternary copolymers) can be listed. The bonding form of the copolymer can be random or block. There is no particular restriction on other comonomers, for example, α-olefins, ethylene compounds, etc. can be listed. Other comonomers can be used alone or in combination of two or more. There is no particular restriction on α-olefins, for example, α-olefins with 3 to 20 carbon atoms can be listed, specifically, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, etc. Among these, from the viewpoint of further improving the heat resistance and strength of molded bodies such as films and fibers, other comonomers are preferably propylene and / or 1-butene. The vinyl compound is not particularly limited, and examples thereof include vinylcyclohexane, styrene, and derivatives thereof, etc. In addition, as other comonomers, non-conjugated polyenes such as 1,5-hexadiene and 1,7-octadiene may be used as necessary.

[0055] The polyethylene composition of this embodiment can be used in the form of a mixture mixed (blended) with ethylene polymers having different viscosity-average molecular weights, molecular weight distributions, etc., or can be used in the form of a mixture mixed (blended) with other resins such as low-density polyethylene, linear low-density polyethylene, polypropylene, polystyrene, etc.

[0056] In the elution temperature-cumulative elution amount curve of CFC, the cumulative elution ratio of the polyethylene composition of the present embodiment from 50°C to 98°C is 50% by mass or more and less than 80% by mass, preferably 52% by mass or more and less than 78% by mass, more preferably 54% by mass or more and less than 76% by mass, and particularly preferably 56% by mass or more and less than 74% by mass. The above-mentioned cumulative elution ratio is within the above-mentioned range, which means that the ratio of the low molecular weight component and the high molecular weight component of the polyethylene composition of the present embodiment is within the range required for achieving both the strength and the fusing performance of the separator.

[0057] Here, the elution temperature-cumulative elution amount curve of CFC can be obtained by the following method.

[0058] The column of the CFC measuring device containing the filler is heated to 140°C, and 20 ml of a sample solution (sample concentration: 1.0 mg / ml) of polyethylene dissolved in o-dichlorobenzene is introduced and maintained for 120 minutes. Next, the column temperature is cooled to 40°C at a cooling rate of 0.5°C / min, and then maintained for 20 minutes. Thereafter, the column temperature is adjusted as follows. First, the temperature is raised to 50°C and maintained at 50°C, and then the temperature is raised to 60°C and maintained at 60°C. Furthermore, the temperature is raised and maintained at intervals of 5°C from 60°C to 75°C, the temperature is raised and maintained at intervals of 3°C from 75°C to 90°C, and the temperature is raised and maintained at intervals of 1°C from 90°C to 120°C. It should be noted that in each heating process, the temperature is raised at a rate of 20°C / min, and each holding temperature is maintained for 21 minutes. The concentration (mass %) of the sample (polyethylene) eluted at each holding temperature for 21 minutes was measured, and an elution temperature-elution amount curve and an elution temperature-cumulative elution amount curve were obtained from the holding temperature and the elution sample concentration.

[0059] In addition, in the elution temperature-cumulative elution amount curve, the cumulative elution ratio from 50° C. to 94° C. of the polyethylene composition of the present embodiment is preferably less than 40% by weight, more preferably less than 38% by weight, and further preferably less than 34% by weight. If the cumulative elution ratio up to 94° C. is within the above range, the amount of low molecular weight components is relatively appropriate, and there is a tendency to improve the melting performance without reducing the strength, so it is preferred.

[0060] In addition, in the elution temperature-cumulative elution amount curve, the cumulative elution ratio from 50°C to 94°C of the polyethylene composition of the present embodiment is preferably 10 wt% or more, more preferably 12 wt% or more, and further preferably 14 wt% or more. If the cumulative elution ratio up to 94°C is within the above range, the amount of low molecular weight components is relatively appropriate, and there is a tendency to improve the melting performance without reducing the strength, so it is preferred.

[0061] As a method for adjusting the cumulative elution ratio to within the above range, for example, the following methods can be cited: adjusting the average molecular weight when polymerizing polyethylene, for example, adjusting the amount of chain transfer agent, or forming polyethylene into a mixture of polyethylene with a higher molecular weight and polyethylene with a lower molecular weight, and adjusting their molecular weight and ratio. In order to improve the fusing performance, slit processability and the productivity of the diaphragm (micro-adjustment of the molecular weight of the polyethylene raw material) without reducing the strength of the film, the latter method is preferably used. However, it is usually difficult to uniformly mix polyethylene with a large molecular weight difference, and when it cannot be uniformly mixed, the problem of increasing defects and changes in film properties is generated. As a method for solving this problem, a method of intentionally adding a small amount of low molecular weight components when polymerizing polyethylene can be cited. By polymerizing both at the same time, the components with a high molecular weight and the components with a low molecular weight are evenly dispersed at the time of manufacturing, thereby solving the problem of mixing. In addition, it is also effective to manufacture polyethylene with a higher molecular weight and polyethylene with a low molecular weight by intentionally adding a small amount of low molecular weight components, and to form them into a mixture. Methods for intentionally adding a small amount of low molecular weight components include: feeding the catalyst into the polymerizer from three locations, with one of the feed locations being adjacent to the ethylene feed location; setting two catalyst feed locations away from the ethylene feed location near the liquid surface of the polymerizer, and setting the catalyst feed location close to the ethylene feed location near the bottom of the polymerizer; not setting a baffle in the polymerizer; making the angle of the stirring blades of the polymerizer vertical; intentionally delaying the deactivation of the catalyst in the flash tank, maintaining high temperature and low pressure conditions during the period, etc.

[0062] [Peak of elution temperature-elution amount curve]

[0063] The polyethylene composition of the present embodiment has more than 3 peaks in the elution temperature-elution amount curve. Generally, polyethylene has 1 to 2 peaks in the elution temperature-elution amount curve. In the case of having more than 3 peaks, the fuse function is further excellent, so it is preferred. In order to exhibit the fuse function, polyethylene with a smaller molecular weight is necessary, and in order to fully ensure the strength, polyethylene with a higher molecular weight is necessary. It is believed that in the case of polyethylene with more than 3 peaks, components with a wide range of molecular weights are simultaneously present, so these properties can be taken into account. As a method for having more than 3 peaks, a method of forming a mixture of polyethylene with a higher molecular weight and polyethylene with a lower molecular weight, and adjusting these molecular weights and proportions can be cited.

[0064] [Weight average molecular weight]

[0065] The polyethylene composition of the present embodiment has at least one weight average molecular weight (M) at a temperature of 85°C or more and less than 105°C among the eluted components recovered at every 1°C by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC). w ) is 200,000 or more, preferably 220,000 or more, and more preferably 250,000 or more. By having such a high molecular weight component, there is a tendency to fully ensure the strength of the diaphragm, so it is preferred. w For example, the amount of hydrogen can be adjusted by allowing hydrogen to exist in the polymerization system or by changing the polymerization temperature.

[0066] [Chlorine content]

[0067] The chlorine content (hereinafter also referred to as "total chlorine content") contained in the polyethylene composition of the present embodiment is preferably 50 mass ppm or less, more preferably 20 mass ppm or less, and further preferably 5 mass ppm or less. By having a total chlorine content of 50 mass ppm or less, a polyethylene composition having better thermal stability is obtained, and when a diaphragm is made, their long-term stability is better. In addition, by having a total chlorine content of 5 mass ppm or less, the chlorine-containing component reacts with the antioxidant and heat stabilizer added during processing to generate quinone compounds, which can fully inhibit the yellowing of the battery diaphragm, and is therefore preferred. The total chlorine content contained in the polyethylene composition of the present embodiment can be controlled by the productivity of polyethylene per unit catalyst. The productivity of polyethylene can be controlled by the polymerization temperature, polymerization pressure, and slurry concentration of the reactor during manufacture. In other words, in order to improve the productivity of the polyethylene used in the present embodiment, it is possible to cite increasing the polymerization temperature, increasing the polymerization pressure, increasing the slurry concentration, or combining them. In addition, as another method, the chlorine content can be further reduced by using an inactive gas containing water, etc. in the deactivation process after polymerization.

[0068] [Additive dosage]

[0069] The content of the additive (hereinafter, sometimes referred to as "additive") for the purpose of imparting fluidity of the polyethylene composition of the present embodiment is preferably 5000 mass ppm or less, more preferably 4000 mass ppm or less, and further preferably 3000 mass ppm or less. The additive for the purpose of imparting fluidity is also referred to as a lubricant, and the substance is not particularly limited. As a specific example, calcium stearate, magnesium stearate or zinc stearate can be cited. By adding a lubricant, the fluidity of the polyethylene composition is improved, the productivity is improved, or it is also suitable for processing applications such as stretchability. However, in the use of the diaphragm, the lubricant that oozes out to the surface of the film during film making may cause problems such as adhesion to the roller or retention, so it is set to 5000ppm or less, and production can be appropriately carried out. Therefore, from the perspective of further fully suppressing the seepage while maintaining productivity and processing application, the content of the above-mentioned additive is preferably 50 mass ppm or more and 5000 mass ppm or less, more preferably 100 mass ppm or more and 4000 mass ppm or less, and further preferably 150 mass ppm or more and 3000 mass ppm or less.

[0070] [Screening]

[0071] The polyethylene composition of the present embodiment preferably contains a powdery form, that is, polyethylene powder.

[0072] For the polyethylene composition of the present embodiment, when sieving with a sieve having a mesh size of 300 μm based on JIS Z 8815, the proportion of the component remaining on the sieve (the component remaining on the sieve) relative to the entire polyethylene composition is preferably 0.5% by mass or less, more preferably 0.2% by mass or less, and further preferably 0.0% by mass, that is, it does not exist. When the proportion of the component remaining on the sieve is 0.5% by mass or less, there is a tendency to further fully suppress the generation of defects (defects) on the surface of the membrane when the diaphragm is made. In the case where the polyethylene composition of the present embodiment contains polyethylene powder, when the polyethylene powder is sieved with a sieve having a mesh size of 53 μm, 75 μm, 106 μm, 150 μm, 212 μm and 300 μm based on JIS Z 8815, and classified into each category, the weight average molecular weight M1 of the category on the coarsest powder side, the weight average molecular weight M2 of the category with the largest proportion, and the weight average molecular weight M3 of the category on the finest powder side preferably satisfy the relationship of the following formula 1. The polyethylene composition of the present embodiment may include two or more polyethylene powders having different weight average molecular weights, in which case each polyethylene powder preferably satisfies the following formula 1. In formula 1, M1 / M2 is more preferably 0.85 or more and 1.15 or less, and more preferably 0.9 or more and 1.1 or less, and M3 / M2 is more preferably 0.85 or more and 1.15 or less, and more preferably 0.9 or more and 1.1 or less.

[0073] 0.8≤M1 / M2≤1.2 and 0.8≤M3 / M2≤1.2 Formula 1

[0074] Satisfying the above formula 1 means that the molecular weight of the polyethylene powder varies little with the particle size. Whether the micropowder side or the coarse powder side becomes a high molecular weight during polymerization varies depending on the type of catalyst. In addition, in addition to this, the possibility of fouling or unexpected polymerization should also be considered. For example, the coarse powder is scaled and pulverized in the reactor, and as a result, it may be mixed in. On the other hand, the micropowder is easily lifted up in the reactor, and the result may be polyethylene that ends the polymerization with a residence time different from that of ordinary polyethylene. As a result, micropowders and coarse powders sometimes have molecular weights different from those of representative polyethylenes, which, during processing, lead to residual dissolution of the powder, or poor mixing and dispersion. As a method for uniformly controlling the average molecular weight of the polymerization of micropowders and coarse powders, there can be listed: selection of polymerization catalysts, removal of fouling by washing inside the polymerizer and piping, suppression of stirring of the polymerizer, etc. In addition, a method of removing coarse powder and micropowder from the obtained polyethylene powder is also effective.

[0075] The weight average molecular weight of the category mentioned here is the weight average molecular weight M measured by GPC. wFor polyethylene in the high molecular weight region that cannot be measured by GPC, the viscosity average molecular weight measured by a viscometer is used. Among them, M1, M2 and M3 of the same polyethylene are measured by the same measurement method. It should be noted that any method can measure a small amount of sample, but if the sample on the sieve on the coarsest powder side is insufficient for measurement, a sample one level closer to the fine powder side is used for measurement. The same is true for the fine powder side.

[0076] [Torque]

[0077] In the polyethylene composition of the present embodiment, 24 g of liquid paraffin having an average molecular weight of 450 or more and less than 550 is kneaded for 10 minutes at a set temperature of 114° C. and a rotation speed of 5 rpm using a small mixing extruder (labo plastomill) (product of Toyo Seiki Co., Ltd., "main body model 4C150", mixer model: R-60), then 16 g of the above-mentioned polyethylene composition and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane are added, the rotation speed is set to 30 rpm and kneaded for 3 minutes, and then kneaded under the condition of raising the set temperature from 114° C. to 163° C. over 6 minutes. In the torque curve obtained at this time, the difference between the resin temperature when the peak with the largest torque is detected and the resin temperature when the peak with the second largest torque is detected is, for example, 25° C. or less (for example, 10° C. or more and 25° C. or less), preferably 23° C. or less, and more preferably 21° C. or less. In this test, the torque forms the peak with the largest torque when the polyethylene composition swells in the solvent, and forms the second largest torque peak when the resin melts. Therefore, the small temperature difference means that the polyethylene is an easily soluble polyethylene that quickly transitions from swelling to melting, and is mixed more evenly in the extruder, so it is preferred. As a method for reducing the above-mentioned temperature difference, for example, methods such as reducing the average molecular weight of polyethylene, reducing the crystallinity of polyethylene, and reducing the bulk density of polyethylene can be listed, but with respect to the average molecular weight and crystallinity, there is a tendency to reduce the strength of the diaphragm, so these methods are not preferred. As a method for reducing the temperature difference of the torque peak, when the polyethylene composition is in powder form, a method of reducing its bulk density is effective. Specifically, a method of controlling the bulk density by dissolving and removing the carrier of the polymerization catalyst after the polymerization of polyethylene is preferred.

[0078] [Catalyst component]

[0079] The catalyst component used for producing the ethylene-based polymer constituting the polyethylene powder of the present embodiment is not particularly limited, and the ethylene-based polymer of the present embodiment can be produced using a Ziegler-Natta catalyst, a metallocene catalyst, or the like.

[0080] First, the Ziegler-Natta catalyst is described. The Ziegler-Natta catalyst is a catalyst comprising a solid catalyst component [A] and an organometallic compound component [B], wherein the solid catalyst component [A] is soluble in an inert hydrocarbon solvent, and is preferably a catalyst for olefin polymerization produced by reacting an organomagnesium compound (A-1) represented by the following formula 2 with a titanium compound (A-2) represented by the following formula 3.

[0081] (A-1): (M 1 ) α (Mg) β (R 2 ) a (R 3 ) b Y 1 c ...Formula 2

[0082] (Where M 1 is a metal atom belonging to any one of Group 12, Group 13 and Group 14 of the Periodic Table, R 2 and R 3 is a hydrocarbon group having 2 to 20 carbon atoms, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 , R 5 、-SR 6 (In these formulas, R 4 , R 5 and R 6 Each independently represents a hydrocarbon group having 1 to 20 carbon atoms) and any group of a β-keto acid residue, in Y 1 When there are multiple numbers, they can be different from each other. α, β, a, b and c are real numbers that satisfy the following relationship: 0≤α, 0<β, 0≤a, 0≤b, 0≤c, 0<a+b, 0≤b / (α+β)≤2, nα+2β=a+b+c (here, n represents M 1 valence.

[0083] (A-2): Ti(OR 7 ) d X 1 (4-d) ……Formula 3

[0084] (where d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0085] It should be noted that the inert hydrocarbon solvent used in the reaction of (A-1) and (A-2) is not particularly limited, and specific examples include: aliphatic hydrocarbons such as butane, pentane, hexane, and heptane; aromatic hydrocarbons such as benzene, toluene, and xylene; and alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, and decalin.

[0086] First, (A-1) is described. (A-1) is shown in the form of an organic magnesium complex soluble in an inert hydrocarbon solvent, but includes all dihydrocarbyl magnesium compounds and complexes of the compound with other metal compounds. The relationship between the symbols α, β, a, b, and c is nα+2β=a+b+c, which represents the valence of the metal atom and the stoichiometry of the substituent.

[0087] In formula 2, as R 2 and R 3 The hydrocarbon group having 2 or more and 20 or less carbon atoms represented by is not particularly limited, and specifically, is an alkyl group, a cycloalkyl group, or an aryl group, and examples thereof include ethyl, propyl, butyl, propyl, hexyl, octyl, decyl, cyclohexyl, phenyl, etc. Among these, an alkyl group is preferred. In the case of α>0, the metal atom M 1 As for the metal atom, metal atoms belonging to any of Groups 12, 13 and 14 of the periodic table can be used, and examples thereof include zinc, boron, aluminum, etc. Among these, aluminum and / or zinc are preferred.

[0088] Magnesium relative to metal atoms M 1 The ratio β / α is not particularly limited, but is preferably 0.1 to 30, and more preferably 0.5 to 10. In the case of using a predetermined organomagnesium compound with α=0, for example, in R 2 In the case of 1-methylpropyl, etc., it is soluble in an inert hydrocarbon solvent, and such a compound also brings satisfactory results in this embodiment. 2 and R 3 It is preferable to satisfy any one of the following three groups (1), (2) and (3).

[0089] Group (1): preferably R 2 and R 3 At least one of them is a secondary or tertiary alkyl group having 4 to 6 carbon atoms, and more preferably R 2 , R 3 All are alkyl groups having 4 to 6 carbon atoms, and at least one of them is a secondary alkyl group or a tertiary alkyl group.

[0090] Group (2): preferably R 2 and R 3 are alkyl groups with different carbon number, more preferably R 2is an alkyl group having 2 or 3 carbon atoms and R 3 It is an alkyl group having 4 or more carbon atoms.

[0091] Group (3): preferably R 2 and R 3 At least one of them is a hydrocarbon group having 6 or more carbon atoms, and more preferably R 2 , R 3 The total number of carbon atoms contained in the alkyl group is 12 or more.

[0092] These groups are specifically shown below. In group (1), as the secondary alkyl group or tertiary alkyl group having 4 to 6 carbon atoms, specifically, 1-methylpropyl group, 2-methylpropyl group, 1,1-dimethylethyl group, 2-methylbutyl group, 2-ethylpropyl group, 2,2-dimethylpropyl group, 2-methylpentyl group, 2-ethylbutyl group, 2,2-dimethylbutyl group, 2-methyl-2-ethylpropyl group, etc. can be listed. Among these, 1-methylpropyl group is preferred.

[0093] In addition, in group (2), there are no particular restrictions on the alkyl group having 2 or 3 carbon atoms, and specifically, there are ethyl, 1-methylethyl, propyl, etc. Among these, ethyl is preferred. In addition, there are no particular restrictions on the alkyl group having 4 or more carbon atoms, and specifically, there are butyl, pentyl, hexyl, heptyl, octyl, etc. Among these, butyl and / or hexyl are preferred.

[0094] In group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, and specific examples thereof include hexyl, heptyl, octyl, nonyl, decyl, phenyl, and 2-naphthyl. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and / or octyl groups are more preferred.

[0095] Generally, when the number of carbon atoms contained in the alkyl group increases, the catalyst component tends to be easily dissolved in an inert hydrocarbon solvent, and the viscosity of the solution tends to increase. Therefore, it is preferred to use a medium-long chain alkyl group (appropriately long chain alkyl group) in terms of operation. It should be noted that the above-mentioned organomagnesium compound can be used after diluting with an inert hydrocarbon solvent, but even if a trace amount of Lewis basic compounds such as ethers, esters, and amines are contained or remain in the solution, it can be used without problem.

[0096] Next, for Y 1 In Formula 2, Y 1 represents an alkoxy group, a silyloxy group, an allyloxy group, an amino group, an amide group, -N=CR 4 , R 5 、-SR 6 (In these formulas, R 4 , R 5 and R 6Each independently represents any one of a hydrocarbon group having 2 to 20 carbon atoms and a β-keto acid residue.

[0097] In formula 2, as R 4 , R 5 and R 6 As for the hydrocarbon group represented by, it is preferably an alkyl group or an aryl group having 1 to 12 carbon atoms, and more preferably an alkyl group or an aryl group having 3 to 10 carbon atoms. There is no particular limitation, and specific examples thereof include: methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl, etc. Among them, any one of butyl, 1-methylpropyl, 2-methylpentyl and 2-ethylhexyl is preferred.

[0098] In addition, in Formula 2, Y 1 Preferably, it is an alkoxy group or a siloxy group. As an alkoxy group, there is no particular limitation, specifically, it is preferably a methoxy group, an ethoxy group, a propoxy group, a 1-methylethoxy group, a butoxy group, a 1-methylpropoxy group, a 1,1-dimethylethoxy group, a pentoxy group, a hexoxy group, a 2-methylpentoxy group, a 2-ethylbutoxy group, a 2-ethylpentoxy group, a 2-ethylhexyloxy group, a 2-ethyl-4-methylpentoxy group, a 2-propylheptyloxy group, a 2-ethyl-5-methyloctyloxy group, an octyloxy group, a phenoxy group, and a naphthoxy group. Among these, it is more preferably any one of a butoxy group, a 1-methylpropoxy group, a 2-methylpentoxy group, and a 2-ethylhexyloxy group. As a siloxy group, there is no particular limitation, specifically, it is preferably any one of a hydrogen dimethyl siloxy group, an ethyl hydrogen methyl siloxy group, a diethyl hydrogen siloxy group, a trimethyl siloxy group, an ethyl dimethyl siloxy group, a diethyl methyl siloxy group, and a triethyl siloxy group. Among these, any one of a hydrogendimethylsiloxy group, an ethylhydrogenmethylsiloxy group, a diethylhydrogensiloxy group, and a trimethylsiloxy group is more preferable.

[0099] In this embodiment, the synthesis method of (A-1) is not particularly limited, and can be obtained by making a compound belonging to the formula R 2 MgX 1 Japanese R 2 2Mg(R 2 For the above meaning, X 1 is a halogen) and an organomagnesium compound belonging to the formula M 1 R 3 n and M 1 R 3 (n-1) H(M1 and R 3 As mentioned above, n represents M 1 The organic metal compound of any one of the above (with a valence of ) is reacted in an inert hydrocarbon solvent at a temperature of 25° C. to 150° C., and then reacted with the organic metal compound of the formula Y 1 -H(Y 1 The compound represented by Y 1 Among these, an organomagnesium compound soluble in an inert hydrocarbon solvent is reacted with an organomagnesium compound of formula Y 1 In the case of reacting a compound represented by -H, there is no particular restriction on the order of the reaction, and a reaction mixture represented by formula Y can be used. 1 -H represented by the method of the compound represented by formula Y 1 Any of the methods of adding an organomagnesium compound to a compound represented by -H, and adding both of them simultaneously.

[0100] In this embodiment, Y in (A-1) 1 The molar composition ratio c / (α+β) relative to all metal atoms is in the range of 0≤c / (α+β)≤2, preferably 0≤c / (α+β)<1. 1 When the molar composition ratio of (A-1) to all metal atoms is 2 or less, the reactivity of (A-2) tends to increase.

[0101] Next, (A-2) is described. (A-2) is a titanium compound represented by Formula 3.

[0102] (A-2): Ti(OR 7 ) d X 1 (4-d) ……Formula 3

[0103] (where d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0104] In the above formula 3, d is preferably 0 or more and 1 or less, and d is more preferably 0. In the formula 3, as R 7 The hydrocarbon group represented by is not particularly limited, and specifically, examples thereof include aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl; and aromatic hydrocarbon groups such as phenyl and naphthyl. Among these, aliphatic hydrocarbon groups are preferred. 1As for the halogen represented by, chlorine, bromine and iodine can be listed. Among these, chlorine is preferred. In this embodiment, (A-2) is more preferably titanium tetrachloride. In this embodiment, one of the compounds selected from the above can be used alone or in combination of two or more.

[0105] Next, the reaction of (A-1) and (A-2) is described. The reaction is preferably carried out in an inert hydrocarbon solvent, more preferably in an aliphatic hydrocarbon solvent such as hexane or heptane. There is no particular restriction on the molar ratio of (A-1) to (A-2) in the above reaction, and the molar ratio (Ti / Mg) of the Ti atoms contained in (A-2) to the Mg atoms contained in (A-1) is preferably 0.1 or more and 10 or less, more preferably 0.3 or more and 3 or less. There is no particular restriction on the reaction temperature, but it is preferably in the range of -80°C or more and 150°C or less, and more preferably in the range of -40°C to 100°C. There is no particular restriction on the order of addition of (A-1) and (A-2), and it can be any of the methods of adding (A-2) after (A-1), adding (A-1) after (A-2), and adding (A-1) and (A-2) at the same time, and the method of adding (A-1) and (A-2) at the same time is preferred. In the present embodiment, the solid catalyst component [A] obtained by the above reaction is used in the form of a slurry solution using an inert hydrocarbon solvent.

[0106] As another example of the Ziegler-Natta catalyst component used in the present embodiment, the following olefin polymerization catalyst is preferred, which comprises a solid catalyst component [C] and an organic metal compound component [B], wherein the solid catalyst component [C] is produced by supporting an organic magnesium compound (C-4) soluble in an inert hydrocarbon solvent represented by Formula 6 and a titanium compound (C-5) represented by Formula 7 on a carrier (C-3) prepared by reacting an organic magnesium compound (C-1) soluble in an inert hydrocarbon solvent represented by Formula 4 with a chlorinating agent (C-2) represented by Formula 5.

[0107] (C-1): (M 2 ) γ (Mg) δ (R 8 )e(R 9 ) f (OR 10 ) g ……Formula 4

[0108] (Where M 2 is a metal atom belonging to any one of Group 12, Group 13 and Group 14 of the Periodic Table, R 8 , R 9 and R 10Each is a hydrocarbon group having 2 to 20 carbon atoms, γ, δ, e, f, and g are real numbers satisfying the following relationship: 0≤γ, 0<δ, 0≤e, 0≤f, 0≤g, 0<e+f, 0≤g / (γ+δ)≤2, kγ+2δ=e+f+g (here, k represents M 2 valence.

[0109] (C-2): H h SiCl i R 11 (4-(h+i)) ...Formula 5

[0110] (Where R 11 is a hydrocarbon group having 1 to 12 carbon atoms, and h and i are real numbers satisfying the following relationship: 0<h, 0<i, 0<h+i≤4)

[0111] (C-4): (M 1 ) α (Mg) β (R 2 ) a (R 3 ) b Y 1 c ...Formula 6

[0112] (Where M 1 is a metal atom belonging to any one of Group 12, Group 13 and Group 14 of the Periodic Table, R 2 and R 3 is a hydrocarbon group having 2 to 20 carbon atoms, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 , R 5 、-SR 6 (In these formulas, R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms) and a β-keto acid residue, in Y 1 If there are multiple 1 They may be different, and α, β, a, b, and c are real numbers satisfying the following relationship: 0≤α, 0<β, 0≤a, 0≤b, 0≤c, 0<a+b, 0≤b / (α+β)≤2, nα+2β=a+b+c (here, n represents M 1 valence.

[0113] (C-5): Ti(OR 7 ) d X 1 (4-d) ...Formula 7

[0114] (where d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0115] First, (C-1) is described. (C-1) is shown in the form of an organic magnesium complex soluble in an inert hydrocarbon solvent, but includes all dihydrocarbyl magnesium compounds and complexes of the compound with other metal compounds. The relationship between the symbols γ, δ, e, f and g in formula 4, kγ+2δ=e+f+g, represents the stoichiometry of the valence of the metal atom and the substituent.

[0116] In the above formula, R 8 or R 9 The hydrocarbon group represented by is not particularly limited, and specifically, each is an alkyl group, a cycloalkyl group or an aryl group, and examples thereof include methyl, ethyl, propyl, butyl, propyl, hexyl, octyl, decyl, cyclohexyl, phenyl, etc. Among these, R is preferably 8 and R 9 Each is an alkyl group. In the case of α>0, the metal atom M 2 As for the metal atom, any metal atom belonging to Group 12, Group 13 and Group 14 of the periodic table can be used, and examples thereof include zinc, boron, aluminum, etc. Among these, aluminum and zinc are preferred.

[0117] Magnesium relative to metal atoms M 2 The ratio δ / γ is not particularly limited, but is preferably 0.1 to 30, and more preferably 0.5 to 10. In addition, when a predetermined organomagnesium compound having γ=0 is used, for example, in R 8 In the case of 1-methylpropyl, etc., it is soluble in an inert hydrocarbon solvent, and such a compound also brings satisfactory results in this embodiment. 8 , R 9 Any one of the following three groups (1), (2) and (3) is preferred.

[0118] Group (1): R 8 , R 9 At least one of them is preferably a secondary or tertiary alkyl group having 4 to 6 carbon atoms, and more preferably R 8 , R 9 All of them have 4 to 6 carbon atoms, and at least one of them is a secondary alkyl group or a tertiary alkyl group.

[0119] Group (2): R 8 and R 9 Preferably, they are alkyl groups with different carbon numbers, and more preferably, R 8is an alkyl group with 2 or 3 carbon atoms, R 9 It is an alkyl group having 4 or more carbon atoms.

[0120] Group (3): R 8 and R 9 At least one of them is preferably a hydrocarbon group having 6 or more carbon atoms, and more preferably R 8 and R 9 The total number of carbon atoms contained in the alkyl group is 12 or more.

[0121] The groups represented by these groups (1) to (3) are specifically shown below. In group (1), as the secondary or tertiary alkyl group having 4 to 6 carbon atoms, specifically, 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 2-methylbutyl, 2-ethylpropyl, 2,2-dimethylpropyl, 2-methylpentyl, 2-ethylbutyl, 2,2-dimethylbutyl, 2-methyl-2-ethylpropyl, etc. can be mentioned. Among these, 1-methylpropyl is preferred.

[0122] In addition, in group (2), as the alkyl group having 2 or 3 carbon atoms, ethyl, 1-methylethyl, propyl, etc. can be cited. Among these, ethyl is preferred. In addition, as the alkyl group having 4 or more carbon atoms, there is no particular limitation, and specifically, butyl, pentyl, hexyl, heptyl, octyl, etc. can be cited. Among these, butyl and / or hexyl are preferred.

[0123] In group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, and specific examples thereof include hexyl, heptyl, octyl, nonyl, decyl, phenyl, and 2-naphthyl. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and / or octyl groups are more preferred.

[0124] Generally, when the number of carbon atoms contained in the alkyl group increases, it tends to be easily dissolved in an inert hydrocarbon solvent and the viscosity of the solution tends to increase. Therefore, medium-long chain alkyl groups are preferably used in terms of operation. It should be noted that the above-mentioned organomagnesium compound is used in the form of an inert hydrocarbon solution, but even if a trace amount of Lewis basic compounds such as ethers, esters, and amines are contained or remain in the solution, it can be used without problem.

[0125] Next, the alkoxy group (OR 10 ) is explained. 10 The hydrocarbon group represented by is preferably an alkyl group or aryl group having 1 to 12 carbon atoms, and more preferably an alkyl group or aryl group having 3 to 10 carbon atoms. 10There is no particular limitation, and specific examples include methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl, etc. Among these, any one of butyl, 1-methylpropyl, 2-methylpentyl and 2-ethylhexyl is preferred.

[0126] In this embodiment, there is no particular limitation on the synthesis method of (C-1), but the following method is preferred: 8 MgX 1 Japanese R 8 2Mg(R 8 For the above meaning, X 1 The organomagnesium compound of the group consisting of halogen atoms and the organic magnesium compound of the formula M 2 R 9 k Japanese M 2 R 9 (k-1) H(M 2 , R 9 and k are the above meanings) in an inert hydrocarbon solvent at a temperature of 25°C to 150°C, and then, if necessary, with a 9 (R 9 The above meaning) represents a hydrocarbon alcohol or a hydrocarbon soluble in an inert hydrocarbon solvent having R 9 The alkoxymagnesium compound and / or alkoxyaluminum compound having a hydrocarbon group represented by is reacted.

[0127] In these methods, when an organomagnesium compound soluble in an inert hydrocarbon solvent is reacted with an alcohol, the order of the reaction is not particularly limited, and any of a method of adding alcohol to the organomagnesium compound, a method of adding the organomagnesium compound to the alcohol, or a method of adding both simultaneously can be used. In the present embodiment, there is no particular limitation on the reaction ratio of the organomagnesium compound soluble in an inert hydrocarbon solvent and the alcohol, and as a result of the reaction, the molar composition ratio of the alkoxy group in the obtained alkoxy-containing organomagnesium compound relative to the total metal atoms g / (γ+δ) is 0≤g / (γ+δ)≤2, preferably 0≤g / (γ+δ)<1.

[0128] Next, (C-2) is described. (C-2) is a silicon chloride compound represented by Formula 5 and having at least one Si—H bond.

[0129] (C-2): H h SiCl i R 11(4-(h+i)) ……Formula 5

[0130] (Where R 11 is a hydrocarbon group having 1 to 12 carbon atoms, and h and i are real numbers satisfying the following relationship: 0<h, 0<i, 0<h+i≤4)

[0131] In formula 5, R 11 The hydrocarbon group represented by is not particularly limited, and specifically, it is an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, for example, methyl, ethyl, propyl, 1-methylethyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, phenyl, etc. Among these, an alkyl group having 1 to 10 carbon atoms is preferred, and an alkyl group having 1 to 3 carbon atoms such as methyl, ethyl, propyl, 1-methylethyl, etc. is more preferred. In addition, h and i are numbers greater than 0 that satisfy the relationship of h+i≤4, and i is preferably 2 to 3.

[0132] There are no particular restrictions on these compounds, and specific examples include HSiCl3, HSiCl2CH3, HSiCl2C2H5, HSiCl2(C3H7), HSiCl2(2-C3H7), HSiCl2(C4H9), HSiCl2(C6H5), HSiCl2(4-Cl-C6H4), HSiCl2(CH=CH2), HSiCl2(CH2C6H5), HSiCl2(1-C 10 H7), HSiCl2(CH2CH=CH2), H2SiCl(CH3), H2SiCl(C2H5), HSiCl(CH3)2, HSiCl(C2H5)2, HSiCl(CH3)(2-C3H7), HSiCl(CH3)(C6H5), HSiCl(C6H5)2, etc. These chlorinated silicon compounds can be used alone or in combination of two or more. Among these, HSiCl3, HSiCl2CH3, HSiCl(CH3)2, HSiCl2(C3H7) are preferred, and HSiCl3 and HSiCl2CH3 are more preferred.

[0133] Next, the reaction of (C-1) and (C-2) is described. During the reaction, it is preferred to use an inert hydrocarbon solvent, chlorinated hydrocarbons such as 1,2-dichloroethane, o-dichlorobenzene, and dichloromethane; an ether medium such as diethyl ether and tetrahydrofuran; or a mixed medium thereof to dilute (C-2) before reuse. Among these, inert hydrocarbon solvents are more preferred in terms of catalyst performance. There is no particular restriction on the reaction ratio of (C-1) to (C-2), and the silicon atoms contained in (C-2) are preferably 0.01 mol or more and 100 mol or less, and more preferably 0.1 mol or more and 10 mol or less, relative to 1 mol of magnesium atoms contained in (C-1).

[0134] There is no particular limitation on the reaction method of (C-1) and (C-2). It can be used that (C-1) and (C-2) are simultaneously introduced into a reactor while being reacted, (C-1) is introduced into the reactor after (C-2) is introduced into the reactor in advance, or (C-2) is introduced into the reactor after (C-1) is introduced into the reactor in advance. Among these, the method of introducing (C-2) into the reactor after (C-1) is introduced into the reactor is preferred. The carrier (C-3) obtained by the above reaction is preferably separated by filtration or decantation, and then fully washed with an inert hydrocarbon solvent to remove unreacted substances or by-products.

[0135] The reaction temperature of (C-1) and (C-2) is not particularly limited, but is preferably above 0°C and below 50°C, more preferably above 3°C and below 30°C, and further preferably above 5°C and below 20°C. Carrying out the reaction at a low temperature is preferred because it is easy to grow the particles of the carrier to a larger size. In a method of adding (C-1) and (C-2) simultaneously while introducing them into a reactor and reacting them, it is preferred to adjust the reaction temperature to a prescribed temperature by adjusting the temperature of the reactor to a prescribed temperature in advance and adjusting the temperature in the reactor to a prescribed temperature while adding them simultaneously. In a method of introducing (C-2) into a reactor in advance and then introducing (C-1) into a reactor, it is preferred to adjust the reaction temperature to a prescribed temperature by adjusting the temperature of the reactor into which the silicon chloride compound is introduced to a prescribed temperature and adjusting the temperature in the reactor to a prescribed temperature while introducing the organomagnesium compound into the reactor. In a method in which (C-2) is introduced into a reactor after (C-1) is previously introduced into the reactor, the temperature of the reactor into which (C-1) is introduced is adjusted to a prescribed temperature, and the temperature in the reactor is adjusted to a prescribed temperature while (C-2) is introduced into the reactor, thereby adjusting the reaction temperature to a prescribed temperature. The time for introducing (C-1) and (C-2) into the reactor is preferably more than 3 hours and less than 20 hours, more preferably more than 5 hours and less than 15 hours, and particularly preferably more than 7 hours and less than 13 hours. By reacting for a long time, it is easy to make the particles of the carrier grow larger, so it is preferred. The catalyst carrier made by this method is characterized in that it is usually larger than the carrier used in the Ziegler catalyst, and it is intended to intentionally remain in the polyethylene powder after polymerization. By dissolving it using the method described in the embodiment, there is a large amount of voids inside, so that a polyethylene powder that is more soluble than a normal polyethylene powder is obtained.

[0136] Next, the organomagnesium compound (C-4) is described. (C-4) is represented by the above formula 6.

[0137] (C-4): (M 1 ) α (Mg) β (R 2 ) a (R 3 ) b Y 1 c ...Formula 6

[0138] (Where M 1 is a metal atom belonging to any one of Group 12, Group 13 and Group 14 of the Periodic Table, R 2 and R 3 is a hydrocarbon group having 2 to 20 carbon atoms, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 , R 5 、-SR 6 (In these formulas, R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms) and a β-keto acid residue, and when Y1 is plural, Y 1 They may be different, and α, β, a, b, and c are real numbers that satisfy the following relationship: 0≤α, 0<β, 0≤a, 0≤b, 0<a+b, 0≤b / (α+β)≤2, nα+2β=a+b+c (here, n represents M 1 valence.

[0139] The amount of (C-4) used is preferably 0.1 to 10, more preferably 0.5 to 5, in terms of the molar ratio of the magnesium atoms contained in (C-4) to the titanium atoms contained in (C-5).

[0140] The reaction temperature of (C-4) and (C-5) is not particularly limited, but is preferably in the range of -80°C to 150°C, and more preferably in the range of -40°C to 100°C.

[0141] The concentration of (C-4) when used is not particularly limited, but is preferably 0.1 mol / L or more and 2 mol / L or less, and more preferably 0.5 mol / L or more and 1.5 mol / L or less, based on the titanium atom contained in (C-4). It should be noted that an inert hydrocarbon solvent is preferably used in the dilution of (C-4).

[0142] The order of adding (C-4) and (C-5) in (C-3) is not particularly limited, and any of the methods of adding (C-5) after (C-4), adding (C-4) after (C-5), and adding (C-4) and (C-5) simultaneously can be used. Among these, the method of adding (C-4) and (C-5) simultaneously is preferred. The reaction of (C-4) and (C-5) is carried out in an inert hydrocarbon solvent, preferably using an aliphatic hydrocarbon solvent such as hexane and heptane. The catalyst thus obtained is used as a slurry solution using an inert hydrocarbon solvent.

[0143] Next, (C-5) is described. In the present embodiment, (C-5) is a titanium compound represented by the above formula 7.

[0144] (C-5): Ti(OR 7 ) d X 1 (4-d) ……Formula 7

[0145] (where d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0146] As R in Formula 7 7 The hydrocarbon group represented by is not particularly limited, and specifically, examples thereof include aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl; and aromatic hydrocarbon groups such as phenyl and naphthyl. Among these, aliphatic hydrocarbon groups are preferred. 1 The halogen represented by is not particularly limited, and specific examples thereof include chlorine, bromine, and iodine. Among these, chlorine is preferred. One species selected from the above (C-5) may be used alone or two or more species may be used in combination.

[0147] The amount of (C-5) used is not particularly limited, but is preferably 0.01 to 20, more preferably 0.05 to 10, in terms of molar ratio relative to the magnesium atoms contained in the support (C-3).

[0148] The reaction temperature of (C-5) is not particularly limited, but is preferably in the range of -80°C to 150°C, and more preferably in the range of -40°C to 100°C. In the present embodiment, the method for supporting (C-5) on (C-3) is not particularly limited, and a method of reacting an excess of (C-5) with (C-3), a method of efficiently supporting (C-5) by using a third component, and a method of supporting by reacting (C-5) with an organomagnesium compound (C-4) are preferred.

[0149] Next, the organometallic compound component [B] in the present embodiment is described. The solid catalyst component of the present embodiment becomes a highly active polymerization catalyst by combining with the organometallic compound component [B]. The organometallic compound component [B] is sometimes also referred to as a "co-catalyst". As the organometallic compound component [B], it is preferably a compound containing a metal belonging to any one of Group 1, Group 2, Group 12 and Group 13 of the periodic table, and is particularly preferably an organoaluminum compound and / or an organomagnesium compound.

[0150] As the organoaluminum compound, it is preferred to use a compound represented by the following formula 8 alone or in combination.

[0151] AHr 12 j Z 1 (3-j) ...Formula 8

[0152] (Where R 12 is a hydrocarbon group having 1 to 20 carbon atoms, Z 1 is a group belonging to the group consisting of hydrogen, halogen, alkoxy, allyloxy, and siloxy, and j is a number of 2 to 3.)

[0153] In the above formula 8, R 12 The hydrocarbon group having a carbon number of 1 or more and 20 or less represented by is not particularly limited, and specifically, includes any one of aliphatic hydrocarbons, aromatic hydrocarbons, and alicyclic hydrocarbons. As a compound represented by formula 8, for example, preferably: trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, tri(2-methylpropyl)aluminum (or triisobutylaluminum), tripentylaluminum, tri(3-methylbutyl)aluminum, trihexylaluminum, trioctylaluminum, tridecylaluminum and other trialkylaluminum; diethylaluminum chloride, ethylaluminum dichloride, bis(2-methylpropyl)aluminum chloride, ethylaluminum sesquichloride, diethylaluminum bromide and other aluminum halide compounds; ethoxydiethylaluminum, butoxydi(2-methylpropyl)aluminum and other alkoxyaluminum compounds; dimethylhydrogensilyloxydimethylaluminum, ethylmethylhydrogensilyloxydiethylaluminum, ethyldimethylsilyloxydiethylaluminum and other siloxyaluminum compounds; and mixtures thereof. Among these, trialkylaluminum compounds are more preferred.

[0154] As the organic magnesium compound, an organic magnesium compound represented by Formula 4 which is soluble in an inert hydrocarbon solvent is preferred.

[0155] (M 2 ) γ (Mg) δ (R 8 ) e (R 9 ) f(OR 10 ) g Formula 4

[0156] (Where M 2 is a metal atom belonging to any one of Group 12, Group 13 and Group 14 of the Periodic Table, R 8 , R 9 and R 10 Each is a hydrocarbon group having 2 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers satisfying the following relationship: 0≤γ, 0<δ, 0≤e, 0≤f, 0≤g, 0<e+f, 0≤g / (γ+δ)≤2, kγ+2δ=e+f+g (here, k represents M 2 valence.

[0157] The organomagnesium compound is shown as an organomagnesium complex soluble in an inert hydrocarbon solvent, but includes all dialkylmagnesium compounds and complexes of the compound with other metal compounds. 2 , R 8 , R 9 , OR 10 As described above, the organic magnesium compound preferably has high solubility in an inert hydrocarbon solvent, and therefore β / α is preferably in the range of 0.5 to 10. In addition, M is further preferably 2 Aluminum compounds.

[0158] There is no particular limitation on the method of adding the solid catalyst component and the organometallic compound component [B] to the polymerization system under polymerization conditions. The two components may be added to the polymerization system separately or reacted in advance before being added to the polymerization system. In addition, there is no particular limitation on the ratio of the two components to be combined. The organometallic compound component [B] is preferably 1 mmol or more and 3000 mmol or less relative to 1 g of the solid catalyst component.

[0159] Next, the metallocene catalyst is described. The metallocene catalyst of the present embodiment is not particularly limited, and is preferably a supported constrained geometry metallocene catalyst prepared from at least (A) a carrier material (hereinafter, also referred to as "component (A)", "(A)"), (B) an organoaluminum compound (hereinafter, also referred to as "component (B)", "(B)"), (C) a transition metal compound having a cyclic η-bonded anionic ligand (hereinafter, also referred to as "component (C)", "(C)"), and (D) an activator capable of reacting with the transition metal compound having a cyclic η-bonded anionic ligand to form a complex exhibiting catalytic activity (hereinafter, also referred to as "component (D)", "(D)")

[0160] As the (a) carrier material, it can be any of an organic carrier and an inorganic carrier. There is no particular limitation on the organic carrier, and examples thereof include (copolymer) polymers of α-olefins having 2 to 10 carbon atoms. As (copolymer) polymers of α-olefins having 2 to 10 carbon atoms, examples thereof include: polyethylene, polypropylene, polybutene-1, ethylene-propylene copolymer, ethylene-butene-1 copolymer, ethylene-hexene-1 copolymer, propylene-butene-1 copolymer, propylene-divinylbenzene copolymer; aromatic unsaturated hydrocarbon polymers, such as polystyrene, styrene-divinylbenzene copolymer; and polar group-containing polymers, such as polyacrylate, polymethacrylate, polyacrylonitrile, polyvinyl chloride, polyamide, and polycarbonate. The above-mentioned inorganic carrier is not particularly limited, for example, inorganic oxides such as SiO2, Al2O3, MgO, TiO2, B2O3, CaO, ZnO, BaO, ThO, SiO2-MgO, SiO2-Al2O3, SiO2-V2O5, etc.; inorganic halogen compounds such as MgCl2, AlCl3, MnCl2, etc.; inorganic carbonates, sulfates and nitrates such as Na2CO3, K2CO3, CaCO3, MgCO3, Al2(SO4)3, BaSO4, KNO3, Mg(NO3)2, etc.; hydroxides such as Mg(OH)2, Al(OH)3, Ca(OH)2, etc. Among these, the preferred carrier material is SiO2. As for the particle size of the carrier material, it can be set to any value, preferably 1.0 μm or more and 100 μm or less, more preferably 2.0 μm or more and 50 μm or less, and further preferably 3.0 μm or more and 10 μm or less.

[0161] The (a) support material is preferably treated with the (b) organoaluminum compound as required. The preferred (b) organoaluminum compound is not particularly limited, and examples thereof include: alkylaluminums such as trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, and trioctylaluminum; alkylaluminum hydrides such as diethylaluminum hydride and diisobutylaluminum hydride; alkoxides such as ethoxydiethylaluminum and methoxydimethylaluminum; and aluminoxanes such as methylaluminoxane, isobutylaluminoxane, and methylisobutylaluminoxane. Among these, trialkylaluminums and alkoxides are preferred, and trimethylaluminum, triethylaluminum, and triisobutylaluminum are more preferred.

[0162] The supported constrained geometry metallocene catalyst may include (c) a transition metal compound having a cyclic η-bonding anionic ligand (hereinafter, also referred to as “transition metal compound”). The transition metal compound of this embodiment is not particularly limited, and may be represented by the following formula 9, for example.

[0163] L l MX p X' q ...Formula 9

[0164] In Formula 9, M represents a transition metal belonging to Group 4 of the periodic table and having an oxidation number of +2, +3 or +4 and forming an η5 bond with one or more ligands L.

[0165] In Formula 9, each L independently represents a cyclic η-bonding anionic ligand. The cyclic η-bonding anionic ligand is a cyclopentadienyl group, an indenyl group, a tetrahydroindenyl group, a fluorenyl group, a tetrahydrofluorenyl group or an octahydrofluorenyl group, and these groups may arbitrarily have 1 to 8 substituents independently selected from a hydrocarbon group containing no more than 20 non-hydrogen atoms, a halogen, a halogenated hydrocarbon group, an aminohydrocarbon group, a hydrocarbonoxy group, a dihydrocarbonamino group, a hydrocarbon phosphino group, a silyl group, an aminosilyl group, a hydrocarbonoxysilyl group and a halogenated silyl group, and further, two Ls may be bonded through a divalent substituent such as a hydrocarbon diyl group containing no more than 20 non-hydrogen atoms, a halogenated hydrocarbon diyl group, an oxyalkylene group, an alkylamino group, a silane diyl group, a halogenated silane diyl group, an aminosilane diyl group or an aminosilyl group.

[0166] In Formula 9, X's each independently represent a monovalent anionic σ-bonded ligand having no more than 60 non-hydrogen atoms, a divalent anionic σ-bonded ligand divalently bonded to M, or a divalent anionic σ-bonded ligand each bonded to M and L with a valence of 1. X's each independently represent a neutral Lewis base coordination compound selected from phosphines, ethers, amines, olefins, and conjugated dienes having 4 to 40 carbon atoms.

[0167] In Formula 9, l represents an integer of 1 or 2. p represents an integer of 0, 1 or 2, and when X represents a monovalent anionic σ-bonded ligand or a divalent anionic σ-bonded ligand bonded to M and L with a valence of each monovalent, p represents an integer less than 1 or more than the formal oxidation number of M, and when X represents a divalent anionic σ-bonded ligand bonded to M with a valence of 2, p represents an integer less than 1+1 or more than the formal oxidation number of M. In addition, q represents an integer of 0, 1 or 2. The transition metal compound is preferably a compound in which l represents 1 in Formula 9.

[0168] A preferred example of the transition metal compound is a compound represented by Formula 10 below.

[0169]

[0170] In Formula 10, M represents titanium, zirconium or hafnium having an oxidation number of +2, +3 or +4. 1 Each independently represents hydrogen, hydrocarbon, silyl, germyl, cyano, halogen or a composite group thereof, each of which may have no more than 20 non-hydrogen atoms. In addition, the adjacent R 1 They may be bonded to each other to form a divalent derivative such as a hydrocarbon diyl group, a silane diyl group, or a germane diyl group to form a ring.

[0171] In formula 10, X" independently represents a halogen, a hydrocarbon group, a hydrocarbonoxy group, a hydrocarbon amino group or a silyl group, each of which has no more than 20 non-hydrogen atoms. In addition, two X" can form a neutral conjugated diene having 5 to 30 carbon atoms or a divalent derivative. Y represents -O-, -S-, -NR 3 -or-PR 3 -, Z represents SiR 3 2.CR 3 2. SiR 3 2SiR 3 2.CR 3 2CR 3 2.CR 3 =CR 3 , CR 3 2SiR 3 2 or GeR 3 2. Here, R 3 Each independently represents an alkyl group or an allyl group having 1 to 12 carbon atoms. In addition, n represents an integer of 1 to 3.

[0172] As the transition metal compound, more preferable examples are compounds represented by the following formula 11 and the following formula 12.

[0173]

[0174] In formulas 11 and 12, respectively, R 1 Each independently represents hydrogen, a hydrocarbon group, a silyl group, a germyl group, a cyano group, a halogen group or a composite group thereof, and each may have no more than 20 non-hydrogen atoms. In addition, M represents titanium, zirconium or hafnium. Z, Y, X and X' represent the same groups as those represented in Formula 10.

[0175] In Formulae 11 and 12, p represents 0, 1 or 2, and q represents 0 or 1. When p represents 2 and q represents 0, the oxidation number of M is +4, and X represents a halogen, a hydrocarbon group, a hydrocarbonoxy group, a dihydrocarbylamino group, a dihydrocarbylphosphide group, a hydrocarbon sulfide group, a silyl group, or a composite group thereof, and represents a group having not more than 20 non-hydrogen atoms.

[0176] In formulas 11 and 12, respectively, when p represents 1 and q represents 0, the oxidation number of M is +3 and X represents a stabilizing anionic ligand selected from allyl, 2-(N,N-dimethylaminomethyl)phenyl and 2-(N,N-dimethyl)-aminobenzyl; or the oxidation number of M is +4 and X represents a derivative of a divalent conjugated diene; or M and X together form a metal cyclopentenyl.

[0177] In formulas 11 and 12, respectively, when p represents 0 and q represents 1, the oxidation number of M is +2 and X' is a neutral conjugated or non-conjugated diene, which can be arbitrarily substituted with one or more hydrocarbon groups. In addition, X' can contain no more than 40 carbon atoms and form a π-type complex with M.

[0178] As the transition metal compound, further preferred examples are compounds represented by the following formula 13 and the following formula 14.

[0179]

[0180] In formulas 13 and 14, respectively, R 1 Each independently represents hydrogen or an alkyl group having 1 to 6 carbon atoms. In addition, M represents titanium, and Y represents -O-, -S-, -NR 3 -、-PR 3 -. Z represents SiR 3 2.CR 3 2. SiR 3 2SiR 3 2.CR 3 2CR 3 2.CR 3 =CR 3 , CR 3 2SiR 3- 2 or GeR 3 2. R 3 Each independently represents hydrogen, or a hydrocarbon group, a hydrocarbonoxy group, a silyl group, a haloalkyl group, a haloallyl group, or a composite group thereof, which may have no more than 20 non-hydrogen atoms. In addition, as required, the two R 3 Each other or the R in Z 3 R in Y 3 They can combine with each other to form a ring.

[0181] In Formulae 13 and 14, p represents 0, 1 or 2, and q represents 0 or 1, respectively. Wherein, when p represents 2 and q represents 0, the oxidation number of M is +4 and X each independently represents a methyl group or a benzyl group. In addition, when p represents 1 and q represents 0, the oxidation number of M is +3 and X represents a 2-(N,N-dimethyl)aminobenzyl group, or the oxidation number of M is +4 and X represents a 2-butene-1,4-diyl group. In addition, when p represents 0 and q represents 1, the oxidation number of M is +2 and X' represents 1,4-diphenyl-1,3-butadiene or 1,3-pentadiene. Regarding these dienes, asymmetric dienes that form metal complexes are exemplified, but are actually mixtures of geometric isomers.

[0182] The supported constrained geometry metallocene catalyst comprises (D) an activator (hereinafter, also referred to as "activator") capable of reacting with a transition metal compound to form a complex exhibiting catalytic activity. Generally speaking, in a metallocene catalyst, a transition metal compound and a complex formed by the above-mentioned activator show high olefin polymerization activity as a catalytically active substance. In the present embodiment, there is no particular limitation on the activator, and for example, a compound represented by the following formula 15 can be cited.

[0183] [LH] d+ [M m Q p ] d- ...Formula 15

[0184] In formula 15, [LH] d+ represents a proton-donating Bronsted acid, and Li represents a neutral Lewis base. m Q p ] d- represents a compatible non-coordinating anion, M represents a metal or metalloid selected from Groups 5 to 15 of the periodic table, and Q each independently represents a hydride, a dialkylamino group, a halide, an alkoxy group, an allyloxy group, a hydrocarbon group, or a substituted hydrocarbon group having no more than 20 carbon atoms, and the number of Q as a halide is 1 or less. In addition, m represents an integer of 1 to 7, p represents an integer of 2 to 14, and d represents an integer of 1 to 7, and pm=d.

[0185] A more preferred example of the activator is a compound represented by Formula 16 below.

[0186] [LH] d+ [M m Q n (G q (TH) r ) Z ] d- ...Formula 16

[0187] In formula 16, [LH] d+ represents a proton-donating Bronsted acid, and L represents a neutral Lewis base. m Q n (G q (TH) r ) Z ] d-represents a compatible non-coordinating anion, M represents a metal or metalloid selected from Groups 5 to 15 of the periodic table, Q each independently represents a hydride, a dialkylamino group, a halide, an alkoxy group, an allyloxy group, a hydrocarbon group, or a substituted hydrocarbon group having no more than 20 carbon atoms, and the number of Q as a halide is 1 or less. In addition, G represents a polyvalent hydrocarbon group having a valence of r+1 bonded to M and T, and T represents O, S, NR or PR. Here, R represents a hydrocarbon group, a trihydrocarbylsilyl group, a trihydrocarbylgermanyl group or hydrogen. In addition, m represents an integer of 1 to 7, n represents an integer of 0 to 7, q represents an integer of 0 or 1, r represents an integer of 1 to 3, z represents an integer of 1 to 8, d represents an integer of 1 to 7, and n+zm=d.

[0188] A further preferred example of the activator is a compound represented by Formula 17 below.

[0189] [LH] + [BQ3Q 1 ] - ‥‥Formula 17

[0190] In formula 17, [LH] + represents a proton-donating Bronsted acid, and L represents a neutral Lewis base. 1 ] - represents a compatible non-coordinating anion, B represents a boron element, and Q each independently represents a pentafluorophenyl group, Q 1 It represents a substituted allyl group having 6 to 20 carbon atoms and having one OH group as a substituent.

[0191] The above-mentioned proton-donating Bronsted acid is not particularly limited, and examples thereof include trialkyl-substituted ammonium cations such as triethylammonium, tripropylammonium, tri(n-butyl)ammonium, trimethylammonium, tributylammonium, tri(n-octyl)ammonium, diethylmethylammonium, dibutylmethylammonium, dibutylethylammonium, dihexylmethylammonium, dioctylmethylammonium, didecylmethylammonium, didodecylmethylammonium, didotetradecylmethylammonium, didoctadecylmethylammonium, didicosylmethylammonium, and di(hydrogenated tallow alkyl)methylammonium; N,N-dimethylaniline N,N-Diethylaniline N,N-2,4,6-Pentamethylaniline and N,N-dimethylbenzylaniline N,N-Dialkylaniline Cation; trityl cation.

[0192] The compatible non-coordinating anions are not particularly limited, and examples thereof include triphenyl(hydroxyphenyl)borate, diphenyldi(hydroxyphenyl)borate, triphenyl(2,4-dihydroxyphenyl)borate, tri(p-tolyl)(hydroxyphenyl)borate, tri(pentafluorophenyl)(hydroxyphenyl)borate, tri(2,4-dimethylphenyl)(hydroxyphenyl)borate, tri(3,5-dimethylphenyl)(hydroxyphenyl)borate, tri(3,5-di(trifluoromethylphenyl))(hydroxyphenyl)borate, tri(pentafluorophenyl)(2-hydroxyethyl)borate, tri(pentafluorophenyl)(4-hydroxybutyl)borate, tri(pentafluorophenyl)(4-hydroxycyclohexyl)borate, tri(pentafluorophenyl)(4-(4'-hydroxyphenyl)phenyl)borate, and tri(pentafluorophenyl)(6-hydroxy-2-naphthyl)borate. These compatible non-coordinating anions are also referred to as "borate compounds". From the viewpoint of catalytic activity and the viewpoint of reducing the total content of Al, Mg, Ti, Zr and Hf, the activator of the supported constrained geometry metallocene catalyst is preferably a borate compound. Preferred borate compounds include tris(pentafluorophenyl)(hydroxyphenyl)borate.

[0193] As the activator, an organic metal oxide compound having a unit represented by Formula 18 below can be used.

[0194]

[0195] (In Formula 18, M 2 represents a metal or metalloid of Group 13 to Group 15 of the Periodic Table, R each independently represents a hydrocarbon group or a substituted hydrocarbon group having 1 to 12 carbon atoms, and n represents a metal M 2 , m represents an integer greater than 2. )

[0196] Another preferred example of the activator is an organoaluminum oxy-compound including a unit represented by Formula 19 below.

[0197]

[0198] (In Formula 19, R represents an alkyl group having 1 to 8 carbon atoms, and m represents an integer of 2 to 60.)

[0199] A more preferred example of the activator is methylaluminoxane containing a unit represented by Formula 20 below.

[0200]

[0201] (In formula 20, m represents an integer from 2 to 60.)

[0202] In addition to the above components (a) to (d), an organoaluminum compound may be used as a catalyst as necessary. The organoaluminum compound is not particularly limited, and examples thereof include compounds represented by the following formula 21.

[0203] AHr n X 3-n ...Formula 21

[0204] In Formula 21, R represents a linear, branched or cyclic alkyl group having 1 to 12 carbon atoms or an allyl group having 6 to 20 carbon atoms, X represents a halogen, hydrogen or an alkoxy group, and n represents an integer of 1 to 3. The organoaluminum compound may be a mixture of compounds represented by Formula 21.

[0205] The catalyst can be obtained by loading component (B), component (C) and component (D) on component (A). The method for loading component (B), component (C) and component (D) is not particularly limited, and examples thereof include: dissolving component (B), component (C) and component (D) in an inert solvent in which each component can be dissolved, mixing with component (A), and then distilling off the solvent; dissolving component (B), component (C) and component (D) in an inert solvent, then concentrating them within a range where solids do not precipitate, and then adding component (A) in an amount that can keep the total amount of the concentrated solution in the particles; loading component (B) and component (D) on component (A) first, and then loading component (C); loading component (B), component (D) and component (C) on component (A) in sequence. Component (C) and component (D) of the present embodiment are preferably liquid or solid. In addition, component (B), component (C) and component (D) are sometimes used by diluting in an inert solvent when loaded.

[0206] The above-mentioned inert solvent is not particularly limited, and examples thereof include: aliphatic hydrocarbons such as isobutane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and mixtures thereof. The inert solvent is preferably used by removing impurities such as water, oxygen, and sulfur using a desiccant, an adsorbent, or the like. The amount of component (B) in terms of Al atoms is preferably 1.0×10 -5 mol~1.0×10 - 1 mol, more preferably 1.0×10 -4 mol~5.0×10 -2 mol, component (C) is preferably 1.0×10 -7 mol~1.0×10 - 3 mol, more preferably 5.0×10 -7mol~5.0×10 -4 mol, component (D) is preferably 1.0×10 -7 mol~1.0×10 - 3 mol, more preferably 5.0×10 -7 mol~5.0×10 -4 The amount of each component used and the loading method are determined based on the activity, economy, powder characteristics, and scaling in the reactor. The obtained supported constrained geometry metallocene catalyst can also be washed using an inert solvent by decantation, filtration, etc. in order to remove the organoaluminum compound, borate compound, and titanium compound that are not supported on the carrier.

[0207] The above series of dissolving, contacting, washing and other operations are preferably carried out at a temperature of -30°C or higher and 80°C or lower selected for each unit operation. The more preferred range of such temperature is 0°C or higher and 50°C or lower. In addition, the series of operations for obtaining the supported constrained geometry metallocene catalyst are preferably carried out in an inactive atmosphere after drying.

[0208] Regarding the supported constrained geometry metallocene catalyst, it can be used alone for homopolymerization of ethylene or copolymerization of ethylene and α-olefins, but in order to prevent poisoning of the solvent and the reaction, it can also be used in the coexistence of an organic aluminum compound as an additional component. There is no particular limitation on the preferred organic aluminum compound, for example, alkyl aluminums such as trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, trihexyl aluminum, and trioctylaluminum; alkyl aluminum hydrides such as diethyl aluminum hydride and diisobutyl aluminum hydride; alkoxide aluminums such as ethoxydiethyl aluminum; aluminoxanes such as methylaluminoxane, isobutyl aluminumoxane, and methylisobutyl aluminumoxane. Among these, trialkyl aluminum and alkoxide aluminum are preferred. More preferred is triisobutyl aluminum.

[0209] [Method for producing ethylene polymer]

[0210] The polymerization method in the manufacture method of the ethylene-based polymer of the present embodiment can be enumerated by suspension polymerization or gas phase polymerization to make ethylene or the method for (co)polymerization of ethylene containing ethylene monomers. Among these, preferably the suspension polymerization method that can effectively remove the polymerization heat. In the suspension polymerization method, an inert hydrocarbon medium can be used as a medium, and olefin itself can also be used as a solvent.

[0211] There is no particular limitation on the inert hydrocarbon medium. Specifically, examples include: aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, kerosene, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, dichloromethane, etc., or mixtures thereof, etc.

[0212] The polymerization temperature in the method for producing the ethylene polymer of the present embodiment is usually preferably 30° C. or higher and 100° C. or lower, more preferably 35° C. or higher and 90° C. or lower, and further preferably 40° C. or higher and 80° C. or lower. If the polymerization temperature is 30° C. or higher, industrially efficient production is possible. On the other hand, if the polymerization temperature is 100° C. or lower, continuous and stable operation can be performed.

[0213] The polymerization pressure in the method for producing an ethylene-based polymer according to the present embodiment is usually preferably normal pressure or higher and 2 MPa or lower, more preferably 0.1 MPa or higher and 1.5 MPa or lower, and further preferably 0.1 MPa or higher and 1.0 MPa or lower.

[0214] By increasing the amount of comonomer during the polymerization reaction, the comonomer-rich component can be unevenly distributed inside the polyethylene powder. As a result, the center of the powder that is easily dissolved and remains is easily dissolved in liquid paraffin, so it is not easy to produce defects, which is preferred. In addition, the center of the powder is easy to dissolve, so the dissolution rate is also faster, which is preferred.

[0215] In order to increase the amount of comonomers in the process of polyreaction, as the form of polymerization, preferably batch type or a continuous type using a plurality of polymerization devices. Particularly preferably, polymerization is carried out in a continuous type. By continuously supplying ethylene gas, solvent, catalyst, etc. in the polymerization system, and continuously discharging together with the generated ethylene polymer, it is possible to suppress the local high temperature state caused by the rapid reaction of ethylene, and the polymerization system becomes more stable. When ethylene reacts under a uniform state in the system, it is suppressed to generate side chains, double bonds, etc. in the polymer chain or to suppress the generation of low molecular weight components, ultra-high molecular weight bodies due to the decomposition and crosslinking of ethylene polymer, thereby easily generating the crystalline components of ethylene polymer. Thus, it is easy to obtain the crystalline components of sufficient amount required for the intensity of film, microporous membrane, etc. Therefore, a more uniform continuous type in the preferred polymerization system.

[0216] The regulation of the molecular weight of ethylene polymers can be regulated by making hydrogen exist in the polymerization system or changing the polymerization temperature, etc., as described in the specification of German Patent Application Publication No. 3127133. By adding hydrogen as a chain transfer agent in the polymerization system, the molecular weight can be controlled within an appropriate range. When hydrogen is added in the polymerization system, the molar fraction of hydrogen is preferably 0 mol % or more and 30 mol % or less, more preferably 0 mol % or more and 25 mol % or less, and further preferably 0 mol % or more and 20 mol % or less.

[0217] In addition, it is preferred that hydrogen is contacted with the catalyst in advance and then added to the polymerization system from the catalyst introduction tube. After the catalyst is just introduced into the polymerization system, the possibility of becoming a local high temperature state due to the high catalyst concentration near the introduction tube outlet and the rapid reaction of ethylene is increased, but by contacting hydrogen and the catalyst before introducing them into the polymerization system, the initial activity of the catalyst can be suppressed, and the side reaction products that hinder the generation of crystalline components can also be suppressed. Therefore, it is preferred that hydrogen is introduced into the polymerization system in a state of contact with the catalyst.

[0218] For the same reason, the outlet of the catalyst introduction pipe in the polymerization system is preferably arranged at a position as far away from the outlet of the ethylene introduction pipe as possible. Specifically, methods such as introducing ethylene from the bottom of the polymerization liquid and introducing the catalyst from the middle of the liquid surface and the bottom of the polymerization liquid can be cited.

[0219] The solvent separation method in the manufacture method of the ethylene polymer of the present embodiment can be carried out by decantation, centrifugal separation, filter filtration method etc., more preferably the centrifugal separation method with good separation efficiency of ethylene polymer and solvent.The amount of the solvent contained in the ethylene polymer after solvent separation is not particularly limited, and is below 70 mass %, more preferably below 60 mass %, and further preferably below 50 mass % relative to the weight of the ethylene polymer.By drying and removing the solvent in a small amount of state in the solvent contained in the ethylene polymer, there is a tendency that the metal component, low molecular weight component etc. contained in the solvent are not easy to remain in the ethylene polymer.Due to not remaining these components, the crystalline component of ethylene polymer is easily generated, and therefore the crystalline component of sufficient amount required for the strength of film, microporous membrane etc. is easily obtained.Therefore, preferably ethylene polymer and solvent are separated by centrifugal separation.

[0220] The deactivation method of the catalyst used for synthesizing the ethylene polymer of the present embodiment is not particularly limited, and is preferably carried out after the ethylene polymer is separated from the solvent. By introducing a chemical reagent for deactivating the catalyst after separation from the solvent, the precipitation of low molecular weight components, catalyst components, etc. contained in the solvent can be reduced.

[0221] Examples of the chemical agent that deactivates the catalyst system include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, alkynes, and the like.

[0222] The drying temperature in the method for producing the ethylene polymer of the present embodiment is usually preferably 50°C or more and 150°C or less, more preferably 50°C or more and 140°C or less, and further preferably 50°C or more and 130°C or less. If the drying temperature is 50°C or more, effective drying can be performed. On the other hand, if the drying temperature is 150°C or less, drying can be performed under the state of suppressing the decomposition and crosslinking of the ethylene polymer. In the present embodiment, in addition to the above-mentioned components, other known components useful for the manufacture of the ethylene polymer may also be included.

[0223] Example

[0224] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples. Preparation and physical property evaluation of each component in Examples and Comparative Examples were carried out by the following methods.

[0225] (MFR)

[0226] Regarding MFR, the polyethylene powder of each example and comparative example was measured at 190°C and a load of 21.6 kg according to ASTM-D-1238. When the MFR is large, the fluidity is good, and the speed of shutoff at high temperature is increased, so the melting performance is improved, which is preferred. The evaluation criteria are as follows.

[0227] ◎: 5.0g / 10 minutes or more

[0228] ○: less than 5.0 g / 10 minutes and 1.0 g / 10 minutes or more

[0229] ×: less than 1.0g / 10 minutes

[0230] (Apparent density)

[0231] Based on JIS K6891, the polyethylene powder of each example and comparative example was made to flow down until it overflowed a 100cc cylindrical container using a funnel and an orifice, and the excess powder was removed from the upper surface of the container using a scraper or the like. The mass of the polyethylene powder in the container was measured, and the mass of the empty measurement container measured in advance was subtracted from the measured mass to obtain the mass of the polyethylene powder. The bulk density was calculated according to the following formula.

[0232] Bulk density (g / cc) = mass of powder (g) / 100 (cc)

[0233] (Measurement of kneading torque)

[0234] 16 g of polyethylene powder of each example and comparative example and 24 g of liquid paraffin (product name: SMOIL P-350P) manufactured by Matsumura Oil Research Institute Co., Ltd. were placed in a small mixing extruder (main body model 4C150, mixer model: R-60) manufactured by Toyo Seiki Seisaku-sho, Ltd., and kneaded for 10 minutes under the conditions of a set temperature of 114° C. and a rotation speed of 5 rpm. Then, 16 g of polyethylene powder and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Limited were added, the rotation speed was set to 30 rpm, kneaded for 3 minutes, and then the set temperature was raised from 114° C. to 163° C. over 6 minutes. The peak was confirmed based on the graph of the average torque calculated by the small mixing extruder test program Ver. 4.52 (Copyright (C) Toyo Seiki Seisaku-sho, Ltd.).

[0235] (Chlorine content)

[0236] The polyethylene powder of each embodiment and comparative example was burned using an automatic sample combustion device (product "AQF-100" of Mitsubishi Chemical Analytical Technology Co., Ltd.), and then absorbed into an absorption liquid (a mixed solution of Na2CO3 and NaHCO3). The absorption liquid was injected into an ion chromatograph (product "ICS1500" of Dionex, column (separation column: AS12A, guard column: AG12A) "Suppressor ASRS300"), and the chlorine content was measured.

[0237] (Amount of lubricant added)

[0238] The lubricant in the polyethylene powder of each example and comparative example was extracted by Soxhlet extraction using tetrahydrofuran (THF) for 6 hours, and the extracted liquid was separated and quantified by liquid chromatography to determine the amount of lubricant added.

[0239] (Cross fractionation chromatography (CFC) determination)

[0240] The polyethylene powder of each example and comparative example was subjected to CFC measurement using the "Automated 3D analyzer CFC-2" product of Polymer ChAR. A stainless steel microsphere column (outer diameter 3 / 8 inch × length 150 mm) was used as a TREF column, and a total of three columns, 1 "GPC UT-807" product of Shodex and 2 "GMHHRH(S)HT" products of Toso, were used as GPC columns, and o-dichlorobenzene (for high performance liquid chromatography) was allowed to flow at a flow rate of 1.0 ml / min as an eluent.

[0241] The column containing the filler was heated to 140°C, and 20 ml of a sample solution of polyethylene powder dissolved in o-dichlorobenzene (sample concentration: 1.0 mg / ml) was introduced and maintained for 120 minutes. Next, the column temperature was lowered to 40°C at a rate of 0.5°C / min and maintained for 20 minutes. In this step, the sample was precipitated on the surface of the filler.

[0242] Thereafter, the column temperature was adjusted as follows. First, the temperature was raised to 50°C and maintained at 50°C. Next, the temperature was raised to 60°C and maintained at 60°C. Further, the temperature was raised and maintained at intervals of 5°C from 60°C to 75°C, at intervals of 3°C from 75°C to 90°C, and at intervals of 1°C from 90°C to 120°C. It should be noted that in each temperature raising process, the temperature was raised at a rate of 20°C / min, and each holding temperature was maintained for 21 minutes.

[0243] The concentration (mass %) of the sample (polyethylene powder) eluted when the temperature was maintained at each holding temperature for 21 minutes was detected, and an elution temperature-elution amount curve and an elution temperature-cumulative elution amount curve were obtained from the holding temperature and the elution sample concentration. In addition, the weight average molecular weight (M) of the component eluted when the temperature was maintained at each holding temperature for 21 minutes was determined using a GPC column connected to a TREF column. w ).

[0244] (Melting point (DSC) determination)

[0245] Using a DSC-7 differential scanning calorimeter manufactured by PerkinElmer, a DSC curve was obtained according to the following steps and conditions.

[0246] 1) About 5 mg of a sample of the polyethylene powder produced in the examples and comparative examples was placed in an aluminum pan, the temperature was raised to 200° C. at 200° C. / min, and the temperature was maintained at 200° C. for 5 minutes.

[0247] 2) Next, the temperature was lowered from 200°C to 50°C at a rate of 10°C / min, and the temperature was maintained for 5 minutes after the temperature reduction was completed.

[0248] 3) Next, the temperature was increased from 50°C to 200°C at a temperature increase rate of 10°C / min.

[0249] Based on the DSC curve observed in the process of 3), the highest temperature at the melting peak position is taken as the melting point (°C). When the melting point (°C) is less than 135°C, it is indicated that a preferred fusing performance (especially fusing at low temperature) is obtained. The evaluation criteria are as follows.

[0250] Evaluation Benchmarks

[0251] ◎: Less than 132℃.

[0252] ○: 132°C or higher and lower than 135°C.

[0253] ×: Above 135℃.

[0254] (Method for producing microporous membrane)

[0255] 0.3 parts by mass of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant was added to 100 parts by mass of polyethylene powder of each embodiment and comparative example, and dry blended using a rotary drum mixer to obtain a polyethylene mixture. The obtained polyethylene mixture was purged with nitrogen and then fed into a twin-screw extruder via a feeder under a nitrogen atmosphere. Furthermore, 65 parts of liquid paraffin (manufactured by Matsumura Oil Co., Ltd., P-350 (trademark)) were injected into the extruder by side feeding, kneaded at 200°C, extruded from a T-die set at the front end of the extruder, and then immediately cooled and solidified with a casting roll cooled to 25°C to form a gel-like sheet with a thickness of 1200 μm. The gel-like sheet was stretched to 7×7 times using a synchronous biaxial stretching machine at 120°C, and then the stretched film was immersed in methyl ethyl ketone for 30 minutes, the liquid paraffin was extracted and removed, and then dried. Furthermore, heat setting was performed at 125° C. for 3 minutes to obtain a microporous membrane. The physical properties of the obtained membrane were measured by the above-mentioned methods. The results are shown in Table 1.

[0256] (Puncture strength measurement)

[0257] For the microporous membrane produced by the above method, a puncture test was performed using Kato Tech's product "KES-G5 Handheld Compression Tester" (trademark) under the conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 2 mm / second, and the maximum puncture load (N) was measured. If the maximum puncture load (N) is 3.5N or more, it means that the strength is sufficiently excellent. The evaluation criteria are as follows.

[0258] Evaluation Benchmarks

[0259] ◎: 4.0N or more.

[0260] ○: less than 4.0 N and 3.5 N or more.

[0261] △: less than 3.5N and 3.0N or more.

[0262] ×: Less than 3.0N.

[0263] (Evaluation of defects)

[0264] Defects of 50 μm or more (black spots observed when the film is observed with transmitted light) present in the microporous film 250 mm×250 mm produced by the above method were counted by visual inspection. Based on the obtained number, the defects were evaluated according to the following evaluation criteria. The evaluation criteria are as follows.

[0265] Evaluation Benchmarks

[0266] ◎:0 or 1.

[0267] ○: 2 to 4 pieces.

[0268] ×: 5 or more.

[0269] In addition, defects of 20 μm or more were counted and evaluated in the same manner. The evaluation criteria are as follows.

[0270] Evaluation Benchmarks

[0271] ◎:0~10 pcs.

[0272] ○:11~30 pieces.

[0273] ×: 31 or more.

[0274] (Evaluation of Slit Processing)

[0275] The microporous membrane produced by the above method was cut into 250 mm×250 mm pieces with a cutter to prepare 10 strip-shaped microporous membranes each having a length of 250 mm. The cut ends were visually evaluated according to the following evaluation criteria.

[0276] Evaluation Benchmarks

[0277] ◎: Almost no burrs or ripples can be seen on the cut surface

[0278] ○: A small amount of burrs and ripples are observed on the cut surface

[0279] ×: Significant burrs and ripples are observed on the cut surface

[0280] (Evaluation of yellowing (yellowing property) (b value))

[0281] The samples were desolvated without stretching the gel-like sheet produced by a T-die film-making machine, and yellowing (yellowing property) was evaluated by measuring b value using "Spectro Photo Meter TOPSCAN TC-1800MKIII" produced by TOKYO DENSHOKU. The evaluation criteria were as follows.

[0282] Evaluation Benchmarks

[0283] ◎: Less than 2.0

[0284] ○: 2.0 or more and less than 2.3

[0285] ×: 2.3 or more

[0286] (Evaluation of oozing out (roller adhesion))

[0287] Each sample was desolvated without stretching the gel-like sheet made by the T-die film-making machine, and heated at 50°C for 72 hours and cooled at 23°C for 1 hour to obtain a sample. Under the condition of a pulling speed of 8m / min, a 100m sample was brought into contact with a black felt cloth attached to a fixed roller, so that the components exuded to the surface of the sample were aggregated on the felt cloth. The amount of aggregates and the aggregation state were visually observed, and the exudation amount was evaluated as follows. The evaluation criteria are as follows.

[0288] Evaluation Benchmarks

[0289] ◎: No adhesion, or slight but local adhesion

[0290] ○: Adhesion of exudate was observed locally

[0291] ×: A large amount of attachment was observed

[0292] Hereinafter, the method for producing the polyethylene powder used in Examples and Comparative Examples will be described.

[0293] [Preparation of Ziegler Catalyst I]

[0294] (1) Synthesis of carrier A

[0295] 1000 mL of a 2 mol / L hexane solution of hydroxytrichlorosilane was placed in an 8 L stainless steel autoclave that had been fully purged with nitrogen. Next, a mixture of AlMg5(C4H9) and 100 mL of the mixture was stirred at 65°C for 10 hours. 11 2550mL of a hexane solution of an organic magnesium compound represented by (OC4H9)2 (equivalent to 2.68mol of magnesium) was added dropwise to an autoclave, and the reaction was continued while stirring at 10°C for 12 hours. After the reaction was completed, the supernatant was removed, and a solid (carrier A) was obtained by washing 4 times with 1800mL of hexane. The obtained solid was dried, and further separated by a sieve with a mesh size of 20μm to remove fine powder. Carrier A was analyzed, and the amount of magnesium contained in each 1g of carrier A was 8.11mmol, and the average particle size of carrier A was 51μm.

[0296] (2) Preparation of solid catalyst component

[0297] While stirring 1970 mL of hexane slurry containing 110 g of carrier A at 10° C., 110 mL of a 1 mol / L titanium tetrachloride hexane solution and 1 mol / L of a composition formula of AlMg5(C4H9) were added simultaneously over 1 hour. 11 110 mL of a hexane solution of an organic magnesium compound represented by (OSiH)2 was added, and the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed, and the mixture was further washed twice with 1100 mL of hexane to prepare Ziegler catalyst I. The amount of titanium contained in 1 g of Ziegler catalyst I was 0.77 mmol.

[0298] [Preparation of Ziegler Catalyst II]

[0299] (1) Synthesis of carrier B

[0300] 1000 mL of a 2 mol / L hexane solution of hydroxytrichlorosilane was placed in an 8 L stainless steel autoclave that had been fully purged with nitrogen. Next, a mixture of AlMg5(C4H9) and 100 mL of the mixture was stirred at 65°C for 0.5 hours. 11 2550 mL of a hexane solution of an organic magnesium compound represented by (OC4H9)2 (equivalent to 2.68 mol of magnesium) was added dropwise to an autoclave, and the reaction was continued while stirring at 65°C for 0.5 hours. After the reaction was completed, the supernatant was removed, and the solid (carrier B) was obtained by washing 4 times with 1800 mL of hexane. Carrier B was analyzed, and the amount of magnesium contained in 1 g of carrier B was 8.67 mmol, and the average particle size of carrier B was 3 μm.

[0301] (2) Preparation of solid catalyst component

[0302] Ziegler catalyst II was prepared in the same manner as the method for preparing Ziegler catalyst I, except that 110 g of carrier B was used instead of carrier A. The amount of titanium contained in 1 g of Ziegler catalyst II was 0.76 mmol.

[0303] [Preparation of Ziegler Catalyst III]

[0304] 1600 mL of hexane was added to an 8 L stainless steel autoclave that was fully purged with nitrogen. While stirring at 10°C, 800 mL of a 1 mol / L titanium tetrachloride hexane solution and 1 mol / L of a compound having the composition formula AlMg5(C4H9) were added simultaneously over 4 hours. 11800 mL of a hexane solution of an organic magnesium compound represented by (OSiH)2 was added. After the addition, the temperature was slowly raised and the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1600 mL of the supernatant was removed and washed 5 times with 1600 mL of hexane to prepare a Ziegler catalyst III. The amount of titanium contained in 1 g of the Ziegler catalyst III was 2.93 mmol.

[0305] [Preparation of Ziegler Catalyst IV]

[0306] 1600 mL of hexane was added to an 8 L stainless steel autoclave that was fully purged with nitrogen. While stirring at 10°C, 800 mL of a 1 mol / L titanium tetrachloride hexane solution and 1 mol / L of a compound having the composition formula of AlMg5(C4H9) were added simultaneously over 1 hour. 11 800 mL of a hexane solution of an organic magnesium compound represented by (OSiH)2 was added. After the addition, the temperature was slowly raised and the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1600 mL of the supernatant was removed and washed three times with 1600 mL of hexane to prepare a Ziegler catalyst IV. The amount of titanium contained in 1 g of the Ziegler catalyst IV was 3.11 mmol.

[0307] (Preparation of Metallocene Catalyst)

[0308] The average particle size of 15 μm and 700 μm 2 Spherical silica with a surface area of ​​1.500 / g and a particle pore volume of 1.8 mL / g was baked at 500°C for 5 hours under a nitrogen atmosphere to dehydrate and obtain dehydrated silica. The amount of surface hydroxyl groups of dehydrated silica is 1.85 mmol / g per 1 g SiO2. Under a nitrogen atmosphere, 40 g of dehydrated silica was dispersed in 800 mL of hexane in an autoclave with a capacity of 1.8 L to obtain a slurry. The obtained slurry was stirred, and 80 mL of a hexane solution of triethylaluminum (concentration 1 mol / L) was added while further maintaining it at 50°C. It was further stirred for 2 hours to react triethylaluminum with the surface hydroxyl groups of silica, thereby obtaining a component [a] comprising silica treated with triethylaluminum and a supernatant, and the surface hydroxyl groups of the silica treated with triethylaluminum were capped with triethylaluminum. Then, the supernatant in the obtained reaction mixture was removed by decantation, thereby removing the unreacted triethylaluminum in the supernatant. Next, an appropriate amount of hexane was added to obtain 880 mL of hexane slurry of silica treated with triethylaluminum.

[0309] On the other hand, 200 mmol of [(N-tert-butylamino)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter also referred to as "titanium complex") was dissolved in 1000 mL of Isopar E [a trade name of a hydrocarbon mixture manufactured by Exxon Chemical Company (USA)], and AlMg6(C2H5)3(n-C4H9) prepared in advance from triethylaluminum and dibutylmagnesium was added. y 20 mL of a 1 mol / L hexane solution was added, and hexane was further added to obtain a component [b] having a titanium complex concentration of 0.1 mol / L.

[0310] In addition, 5.7 g of di(hydrogenated tallow alkyl)methylammonium tri(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter also referred to as "borate") was added to 50 mL of toluene to dissolve it, and a 100 mmol / L toluene solution of the borate was obtained. At room temperature, 5 mL of a 1 mol / L hexane solution of ethoxydiethylaluminum was added to the toluene solution of the borate, and hexane was further added to make the borate concentration in the solution 70 mmol / L. Thereafter, the mixture was stirred at room temperature for 1 hour to obtain a reaction mixture containing the borate. 46 mL of a reaction mixture containing the borate was added to 800 mL of the slurry of component [a] obtained above while stirring at 15°C to 20°C, and the borate was loaded on silica, thereby obtaining a slurry of silica loaded with borate. 32 mL of component [b] was added to the obtained slurry, stirred for 3 hours, and the titanium complex was reacted with the borate, thereby obtaining a supported metallocene catalyst containing silica and a supernatant and having a catalytically active substance formed on the silica.

[0311] [Example 1]

[0312] (Polymerization and preparation of polyethylene powder A-1)

[0313] Using a Bessel-type 340L polymerization reactor with a stirring device using vertical stirring blades and without baffles, intermittent polymerization was carried out under polymerization conditions of a polymerization temperature of 75°C, a polymerization pressure of 0.8 MPa, and a reaction time of 1.0 hour. Dehydrated n-hexane as a solvent, 11 kg of ethylene as a raw material, 1.5 mmol of a metallocene catalyst as a catalyst in terms of Ti atoms, and 20 mmol of triisobutylaluminum were used. The ethylene feed position was set near the bottom of the polymerization vessel. The catalyst was fed from three locations, two of which were set near the liquid surface, and the remaining location was adjacent to the ethylene feed position located near the bottom. In addition, in order to adjust the molecular weight, hydrogen was introduced into the polymerization reactor in such a way that the amount of hydrogen was 0.075 mol% relative to the gas phase concentration of ethylene and 1-butene combined. In addition, in the last 10 minutes of the polymerization, 1-butene as a comonomer was introduced in such a way that the gas phase concentration relative to ethylene was 5 mol%. The catalytic activity was 7.9×10 4 g-PE / g-metallocene catalyst.

[0314] After the polymerization, the polymerization slurry in the polymerization reactor is introduced into a flash tank at a pressure of 0.05 MPa and a temperature of 90°C, and stirred for 30 minutes. Thereafter, the temperature is set to 70°C to separate the unreacted ethylene, 1-butene and hydrogen. Next, the polymerization slurry introduced into the flash tank is introduced into a buffer tank at a pressure of 0.30 MPa and a temperature of 70°C, and allowed to stand for 1 hour. Next, centrifugal separation is used to separate the polymer from residues other than the polymer (for example, solvents, etc.). The separated polymer is dried while blowing nitrogen at 85°C, and further sieved with a mesh size of 53 μm and a mesh size of 300 μm to remove fine powder and coarse powder, thereby obtaining polyethylene powder A-1. The weight average molecular weight (M) of polyethylene powder A-1 is w ) is 2.51×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0315] (Polymerization and preparation of polyethylene powder A-2)

[0316] In the polymerization reactor, 0.32 mol% of 1-butene as a comonomer was introduced relative to the gas phase concentration of ethylene, and the amount of hydrogen was set to 0.152 mol% relative to the total gas phase concentration of ethylene and 1-butene. Polyethylene powder A-2 was obtained in the same manner as polyethylene powder A-1. The catalytic activity was 9.0×10 4 g-PE / g-metallocene catalyst, weight average molecular weight of polyethylene powder A-2 (M w ) is 1.16×10 5In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0317] (Preparation of Polyethylene Powder B-1)

[0318] The polyethylene powder A-1 and the polyethylene powder A-2 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-1. Table 2 shows the evaluation results of the polyethylene powder B-1.

[0319] A microporous membrane was prepared by the above method using polyethylene powder B-1. The membrane was subjected to CFC measurement, and the same result as that of polyethylene powder B-1 was obtained.

[0320] [Example 2]

[0321] (Polymerization and preparation of polyethylene powder A-3)

[0322] Hexane, ethylene, hydrogen and catalyst were continuously supplied to a Bessel type 300L polymerization reactor having a stirring device using vertical stirring blades and without baffles. The polymerization pressure was set to 0.5MPa and the polymerization temperature was set to 80°C. Hexane was supplied to the vicinity of the bottom surface of the polymerization reactor at 40L / hour. Ziegler catalyst I was used as a catalyst and triisobutylaluminum was used as a cocatalyst. Ziegler catalyst I was added to the polymerization reactor at a rate of 0.2g / hour and triisobutylaluminum was added to the polymerization reactor at a rate of 10mmol / hour. The catalyst was fed from three places, two of which were set near the liquid surface, and the remaining one was adjacent to the feeding position of ethylene located near the bottom surface. The production rate of the obtained ethylene polymer was 10kg / hour. Hydrogen was continuously supplied to the polymerization reactor using a pump in such a way that the amount of hydrogen was 10 mol% relative to the gas phase concentration of ethylene. The catalytic activity was 80000g-PE / g-Ziegler catalyst I. While keeping the horizontal surface of the polymerization reactor constant, the polymerization slurry was continuously introduced into a flash tank at a pressure of 0.05 MPa and a temperature of 90°C, stirred for 30 minutes, and then the temperature was lowered to 70°C to separate the unreacted ethylene and hydrogen. Next, while keeping the horizontal surface of the polymerization reactor constant, the polymerization slurry was continuously sent to a centrifuge to separate the polymer from residues other than the polymer (for example, solvents, etc.). The separated polymer was dried while blowing nitrogen at 85°C, and steam was sprayed on the polymer during drying to deactivate the catalyst and co-catalyst. In order to remove the magnesium chloride inside the obtained polymer, the obtained polymer was put into pure water, stirred for 2 hours, and dried. 600 ppm of calcium stearate (manufactured by Dainichi Chemical Co., Ltd., C60) was added to the obtained polymer, and it was uniformly mixed using a Henschel mixer. The obtained polymer was removed from fine powder and coarse powder using a sieve with a mesh size of 53 μm and a mesh size of 300 μm, thereby obtaining polyethylene powder A-3. M of polyethylene powder A-3 w 4.24×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0323] (Polymerization and preparation of polyethylene powder A-4)

[0324] The polymerization temperature was set to 70°C, 1-butene as a comonomer was introduced into the polymerization reactor in such a manner that the gas phase concentration of 1-butene relative to ethylene was 10.3 mol%, and the amount of hydrogen was set to 17 mol% relative to the total gas phase concentration of ethylene and 1-butene. The polymerization was carried out in the same manner as the polyethylene powder A-3, except that magnesium chloride was removed. The catalytic activity was 1.0×10 5g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm, thereby obtaining polyethylene powder A-4. M of polyethylene powder A-4 w 9.89×10 4 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0325] (Preparation of Polyethylene Powder B-2)

[0326] The polyethylene powder A-3 and the polyethylene powder A-4 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain polyethylene powder B-2. Table 2 shows the evaluation results of polyethylene powder B-2.

[0327] [Comparative Example 1]

[0328] (Preparation of Polyethylene Powder B-12)

[0329] The polyethylene powder A-2 and the polyethylene powder A-4 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-12. Table 2 shows the evaluation results of the polyethylene powder B-12.

[0330] [Comparative Example 2]

[0331] (Preparation of Polyethylene Powder B-7)

[0332] The polyethylene powder A-1 and the polyethylene powder A-2 were mixed at a ratio of 20:80, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-7. Table 2 shows the evaluation results of the polyethylene powder B-7.

[0333] [Example 3]

[0334] (Polymerization and preparation of polyethylene powder A-6)

[0335] The total pressure was set to 0.23 MPa, and the amount of hydrogen was set to 9.7 mol% relative to the gas phase concentration of ethylene. Polymerization and removal of magnesium chloride were carried out in the same manner as polyethylene powder A-3, thereby polymerizing polyethylene having a molecular weight similar to that of A-3 at a low activity. The catalytic activity was 3.3×10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-6. M of polyethylene powder A-6 w 3.95×10 5In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0336] (Polymerization and preparation of polyethylene powder A-7)

[0337] The total pressure was set to 0.21 MPa, 1-butene as a comonomer was introduced into the polymerization reactor at 10.5 mol% relative to the gas phase concentration of ethylene, and the amount of hydrogen was set to 16.1 mol% relative to the total gas phase concentration of ethylene and 1-butene. Polymerization and removal of magnesium chloride were carried out in the same manner as polyethylene powder A-3, thereby polymerizing polyethylene having a molecular weight similar to that of polyethylene powder A-5 at a low activity. The catalytic activity was 3.4×10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-7. M of polyethylene powder A-7 w 8.68×10 4 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0338] (Preparation of Polyethylene Powder B-5)

[0339] The polyethylene powder A-6 and the polyethylene powder A-7 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-5. Table 2 shows the evaluation results of the polyethylene powder B-5.

[0340] [Example 4]

[0341] (Preparation of Polyethylene Powder B-6)

[0342] The polyethylene powder A-3 and the polyethylene powder A-4 were mixed at a ratio of 50:50, 6000 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain polyethylene powder B-6. Table 2 shows the evaluation results of polyethylene powder B-6.

[0343] [Example 5]

[0344] (Polymerization and preparation of polyethylene powder A-14)

[0345] The polymerization and removal of magnesium chloride were carried out in the same manner as in polyethylene powder A-3 except that the amount of hydrogen was set to 7.4 mol% relative to the gas phase concentration of ethylene. The catalytic activity was 9.0×10 4g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-14. M of polyethylene powder A-14 w 8.16×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0346] (Preparation of Polyethylene Powder B-13)

[0347] The polyethylene powder A-4 and the polyethylene powder A-14 were mixed at a ratio of 60:40, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-13. Table 2 shows the evaluation results of the polyethylene powder B-13.

[0348] [Example 6]

[0349] (Polymerization and preparation of polyethylene powder A-8)

[0350] Polymerization was carried out in the same manner as for polyethylene powder A-2 except that the temperature of the flash tank was initially set to 70°C and stirring was not performed for 30 minutes. The catalytic activity was 8.6×10 4 g-PE / g-metallocene catalyst, weight average molecular weight (M w ) is 1.20×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0351] (Polymerization and preparation of polyethylene powder A-9)

[0352] The polymerization was carried out in the same manner as the polyethylene powder A-4 except that the temperature of the flash tank was initially set to 70°C and stirring was not performed for 30 minutes, and magnesium chloride was removed. The catalytic activity was 1.0×10 5 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm, thereby obtaining polyethylene powder A-9. M of polyethylene powder A-9 w 1.04×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0353] (Polymerization and preparation of polyethylene powder A-22)

[0354] Polymerization and removal of magnesium chloride were performed in the same manner as in polyethylene powder A-3, except that the temperature of the flash tank was initially set to 70°C, stirring was not performed for 30 minutes, and the amount of hydrogen was set to 5.6 mol% relative to the gas phase concentration of ethylene. Fine powder and coarse powder were removed from the obtained polymer using a sieve having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-22. M of polyethylene powder A-22 w 1.11×10 6 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0355] (Preparation of Polyethylene Powder B-4)

[0356] Polyethylene powder A-8, polyethylene powder A-9, and polyethylene powder A-22 were mixed at a ratio of 50:20:30, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain polyethylene powder B-4. Table 2 shows the evaluation of polyethylene powder B-4.

[0357] [Example 7]

[0358] (Polymerization and preparation of polyethylene powder A-10)

[0359] The polymerization was carried out in the same manner as that of polyethylene powder A-1 except that no comonomer was introduced during the polymerization. The catalytic activity was 8.0×10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polyethylene powder using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-10. M of polyethylene powder A-10 w 2.37×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0360] (Polymerization and preparation of polyethylene powder A-11)

[0361] The polymerization was carried out in the same manner as the polyethylene powder A-2 except that the amount of the comonomer was kept constant at 0.32 mol % until the end of the polymerization. The catalytic activity was 9.0 × 10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polyethylene powder using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-11. M of polyethylene powder A-11 w 1.41×10 5In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0362] (Preparation of Polyethylene Powder B-10)

[0363] The polyethylene powder A-10 and the polyethylene powder A-11 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain polyethylene powder B-10. Table 2 shows the evaluation results of polyethylene powder B-10.

[0364] [Example 8]

[0365] (Polymerization and preparation of polyethylene powder A-12)

[0366] The polymerization was carried out in the same manner as the polyethylene powder A-3 except that the catalyst was Ziegler catalyst II and magnesium chloride was removed. The catalytic activity was 8.0×10 4 g-PE / g-Ziegler catalyst II. Fine powder and coarse powder were removed from the obtained polyethylene powder using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-12. M of polyethylene powder A-12 w 4.02×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0367] (Polymerization and preparation of polyethylene powder A-13)

[0368] The polymerization was carried out in the same manner as the polyethylene powder A-4 except that the catalyst was Ziegler catalyst II and magnesium chloride was removed. The catalytic activity was 1.0×10 5 g-PE / g-Ziegler catalyst II. Fine powder and coarse powder were removed from the obtained polyethylene powder using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-13. M of polyethylene powder A-13 w 1.04×10 6 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0369] (Preparation of Polyethylene Powder B-11)

[0370] The polyethylene powder A-12 and the polyethylene powder A-13 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-11. Table 2 shows the evaluation results of the polyethylene powder B-11.

[0371] [Example 9]

[0372] (Polymerization and preparation of polyethylene powder A-15)

[0373] The polymerization was carried out in the same manner as the polyethylene powder A-3 except that 1-butene as a comonomer was introduced into the polymerization reactor in such a manner that the gas phase concentration was 2.4 mol% relative to ethylene, and the amount of hydrogen was set to 7.4 mol% relative to the total gas phase concentration of ethylene and 1-butene, and magnesium chloride was removed. The catalytic activity was 8.7×10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm, thereby obtaining polyethylene powder A-4. M of polyethylene powder A-4 w 7.57×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0374] (Preparation of Polyethylene Powder B-16)

[0375] The polyethylene powder A-4 and the polyethylene powder A-15 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-16. Table 2 shows the evaluation results of the polyethylene powder B-16.

[0376] [Example 10]

[0377] (Polymerization and preparation of polyethylene powder A-5)

[0378] The polymerization and removal of magnesium chloride were carried out in the same manner as for polyethylene powder A-3 except that the amount of hydrogen was set to 5.6 mol % relative to the gas phase concentration of ethylene. The catalytic activity was 8.2 × 10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-5. M of polyethylene powder A-5 w 1.12×10 6 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0379] (Polymerization and preparation of polyethylene powder A-16)

[0380] Polyethylene powder A-16 was obtained in the same manner as polyethylene powder A-1 except that 0.10 mol% of 1-butene as a comonomer was introduced into the polymerization reactor relative to the gas phase concentration of ethylene, and the amount of hydrogen was set to 0.047 mol% relative to the total gas phase concentration of ethylene and 1-butene. The catalytic activity was 8.5×10 4 g-PE / g-metallocene catalyst, weight average molecular weight of polyethylene powder A-16 (M w ) is 3.02×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0381] (Preparation of Polyethylene Powder B-17)

[0382] Polyethylene powder A-16, polyethylene powder A-4, and polyethylene powder A-5 were mixed at a ratio of 50:20:30, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain polyethylene powder B-17. Table 2 shows the evaluation of polyethylene powder B-17.

[0383] [Example 11]

[0384] (Preparation of Polyethylene Powder B-15)

[0385] The polyethylene powder A-3 and the polyethylene powder A-14 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain a polyethylene powder B-15. Table 2 shows the evaluation results of the polyethylene powder B-15.

[0386] [Example 12]

[0387] (Polymerization and preparation of polyethylene powder A-18)

[0388] Polyethylene powder A-18 was obtained in the same manner as polyethylene powder A-1 except that the coarse powder was not removed by a sieve with a mesh size of 300 μm. The catalytic activity was 8.0×10 4 g-PE / g-metallocene catalyst, weight average molecular weight of polyethylene powder A-18 (M w ) is 2.62×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0389] (Polymerization and preparation of polyethylene powder A-19)

[0390] Polyethylene powder A-19 was obtained in the same manner as polyethylene powder A-2 except that the coarse powder was not removed by a sieve with a mesh size of 300 μm. The catalytic activity was 8.2×104 g-PE / g-metallocene catalyst, weight average molecular weight of polyethylene powder A-19 (M w ) is 1.23×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0391] (Preparation of Polyethylene Powder B-19)

[0392] The polyethylene powder A-18 and the polyethylene powder A-19 were mixed at a ratio of 50:50, 600 ppm of calcium stearate was added, and the mixture was thoroughly mixed to obtain polyethylene powder B-19. Table 2 shows the evaluation results of polyethylene powder B-19.

[0393] [Comparative Example 3]

[0394] (Polymerization and preparation of polyethylene powder A-17)

[0395] Hexane, ethylene, hydrogen and catalyst were continuously supplied to a Bessel type 300L polymerization reactor with a stirring device. The polymerization pressure was 0.5MPa. The polymerization temperature was maintained at 83°C by jacket cooling. Hexane was supplied from the bottom of the polymerization reactor at 40L / hour. Ziegler catalyst III and triisobutylaluminum as a cocatalyst were used. Ziegler catalyst III was added from the middle of the liquid surface and the bottom of the polymerization reactor at a rate of 0.2g / hour, and triisobutylaluminum was added from the middle of the liquid surface and the bottom of the polymerization reactor at a rate of 10mmol / hour. The production rate of ethylene polymer was 10kg / hour. Hydrogen was continuously supplied by a pump in such a way that the hydrogen concentration relative to ethylene in the gas phase became 14 mol%. It should be noted that in order to make hydrogen contact with the catalyst in advance, hydrogen was supplied from the catalyst inlet pipe and ethylene was supplied from the bottom of the polymerization reactor. The catalytic activity was 80000g-PE / g-Ziegler catalyst III. The polymerization slurry was continuously extracted into a flash tank at a pressure of 0.05 MPa and a temperature of 70°C in such a manner that the horizontal surface of the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated. The polymerization slurry was continuously transported to a centrifuge in such a manner that the horizontal surface of the polymerization reactor was kept constant, and the polymer and other solvents, etc. were separated. The separated ethylene polymer powder was dried while blowing nitrogen at 85°C. It should be noted that in this drying process, steam was sprayed on the powder after polymerization to deactivate the catalyst and the co-catalyst. 1500 ppm of calcium stearate (manufactured by Dainichi Chemical Co., Ltd., C60) was added to the obtained ethylene polymer powder, and it was uniformly mixed using a Henschel mixer. Fine powder and coarse powder were removed from the obtained polymer using a sieve with a mesh size of 53 μm and a mesh size of 300 μm to obtain polyethylene powder A-17. The M of polyethylene powder A-17w 2.45×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0396] (Preparation of Polyethylene Powder B-18)

[0397] 600 ppm of calcium stearate was added to the polyethylene powder A-17 and mixed thoroughly to obtain polyethylene powder B-18. Table 2 shows the evaluation results of polyethylene powder B-18.

[0398] [Example 13]

[0399] (Polymerization and preparation of polyethylene powder A-20)

[0400] In a Bessel type 30L polymerization reactor equipped with a stirring device, 14L (total amount) of hexane was placed, and ethylene and hydrogen (12 mol% to 18 mol% relative to the total amount of ethylene and hydrogen (100 mol%)) were intermittently supplied while changing the hydrogen concentration, and the polymerization pressure was adjusted to 0.5MPa. 0.025mmol of triisobutylaluminum was added as a cocatalyst, and then 0.02g of Ziegler catalyst IV was added, thereby initiating the polymerization reaction. During the polymerization reaction, ethylene was also supplied at a constant rate of 0.5L / min. The polymerization temperature was maintained from 82°C (polymerization initiation rate) to 85°C (maximum temperature reached) by jacket cooling and condenser cooling. After 3 hours, the polymerization temperature was cooled to 60°C, and the reactor was depressurized to remove unreacted ethylene and hydrogen. The polymerization system was replaced with nitrogen, and then the polymerization slurry was injected into methanol to completely stop the polymerization reaction. The slurry concentration is 10.0% by mass, and the catalytic activity is 50,000 g-PE / g-Ziegler catalyst IV. Next, the polymerization slurry is transported to a filter tank with a filter to separate the polymer and the solvent. Thereafter, it is heated and dried at 85°C for 12 hours using a hot air dryer. 600 ppm of calcium stearate (manufactured by Dainichi Chemical Co., Ltd., C60) is added to the obtained polymer and uniformly mixed using a Henschel mixer. The obtained polymer is removed from fine powder and coarse powder using a sieve with a mesh size of 53 μm and a mesh size of 300 μm, thereby obtaining polyethylene powder A-20. The M of polyethylene powder A-20 w is 4.47×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0401] (Preparation of Polyethylene Powder B-20)

[0402] 600 ppm of calcium stearate was added to the polyethylene powder A-20 and mixed thoroughly to obtain polyethylene powder B-20. Table 2 shows the evaluation results of polyethylene powder B-20.

[0403] [Example 14]

[0404] (Polymerization and preparation of polyethylene powder A-21)

[0405] The polymerization was carried out in the same manner as in the polyethylene powder A-3 except that the amount of hydrogen was set to 11.0 mol % relative to the total gas phase concentration of ethylene and 1-butene, and magnesium chloride was removed. The catalytic activity was 8.2×10 4 g-PE / g-Ziegler catalyst I. Fine powder and coarse powder were removed from the obtained polymer using sieves having a mesh size of 53 μm and a mesh size of 300 μm, thereby obtaining polyethylene powder A-21. M of polyethylene powder A-21 w 3.51×10 5 In addition, M1, M2, M3, M1 / M2 and M3 / M2 in the above formula 1 are shown in the following Table 1.

[0406] (Preparation of Polyethylene Powder B-21)

[0407] 600 ppm of calcium stearate was added to the polyethylene powder A-21 and mixed thoroughly to obtain polyethylene powder B-21. Table 2 shows the evaluation results of polyethylene powder B-21.

[0408] [Comparative Example 4]

[0409] (Preparation of Polyethylene Powder B-14)

[0410] Polyethylene powder A-2, polyethylene powder A-4 and polyethylene powder A-14 were mixed at a ratio of 50:10:40, 600 ppm of calcium stearate was added and mixed thoroughly to obtain polyethylene powder B-14. Table 2 shows the evaluation of polyethylene powder B-14.

[0411]

[0412]

[0413] This application is based on Japanese patent application (Japanese Patent Application No. 2017-146829) filed on July 28, 2017, the contents of which are incorporated herein by reference.

[0414] Industrial Applicability

[0415] The polyethylene composition of the present invention can impart excellent strength and fuse performance when processed into a separator and has good slit processability, and is therefore particularly useful as a raw material for a separator.

Claims

1. A polyethylene composition, wherein The MFR of the polyethylene composition is 5.0 g / 10 minutes or more, or less than 5.0 g / 10 minutes and 1.0 g / 10 minutes or more, and the MFR is measured according to ASTM-D-1238 at 190° C. and a load of 21.6 kg. 24 g of liquid paraffin having an average molecular weight of 450 or more and less than 550 was kneaded for 10 minutes at a set temperature of 114° C. and a rotation speed of 5 rpm using a small mixing extruder, and then 16 g of the polyethylene composition and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane were added, the rotation speed was set to 30 rpm and kneaded for 3 minutes, and then kneaded under the condition of raising the set temperature from 114° C. to 163° C. in 6 minutes, and in the torque curve obtained at this time, the difference between the resin temperature when the peak with the largest torque was detected and the resin temperature when the peak with the second largest torque was detected was 25° C. or less, The polyethylene composition contains an additive for imparting fluidity of 4000 ppm by mass or less, In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 94°C is 10% by mass or more, The polyethylene composition has the following characteristics (A) and (B): (A) in an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 50% by mass or more and less than 80% by mass; and (B) in the fractions recovered at 1°C by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC), at least one weight average molecular weight (M) at a temperature of 85°C or more and less than 105°C w ) is an elution component of more than 220,000.

2. The polyethylene composition according to claim 1, wherein When sieving is performed using a sieve having a mesh size of 300 μm based on JIS Z 8815, there are no components remaining on the sieve.

3. The polyethylene composition according to claim 1 or 2, wherein The polyethylene composition has a chlorine content of 50 mass ppm or less.

4. The polyethylene composition according to claim 1 or 2, wherein In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 94°C was less than 40% by mass.

5. The polyethylene composition according to claim 1 or 2, wherein The elution temperature-elution amount curve obtained by measuring the elution amount per 1° C. by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC) has three or more peaks.

6. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains polyethylene powder, When the polyethylene powder is sieved using sieves having mesh sizes of 53 μm, 75 μm, 106 μm, 150 μm, 212 μm, and 300 μm based on JIS Z 8815 and classified into each category, The weight average molecular weight M1 of the coarsest powder category, the weight average molecular weight M2 of the largest proportion category, and the weight average molecular weight M3 of the finest powder category satisfy the relationship of the following formula 1: 0.8≤M1 / M2≤1.2 and 0.8≤M3 / M2≤1.2 Formula 1.

7. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 52% by mass or more and less than 78% by mass.

8. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 54% by mass or more and less than 76% by mass.

9. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 56% by mass or more and less than 74% by mass.

10. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 53.5% by mass or more and less than 80% by mass.

11. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 55.1% by mass or more and less than 80% by mass.

12. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 57.4% by mass or more and less than 80% by mass.

13. The polyethylene composition according to claim 1 or 2, wherein: In an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 50 mass % or more and 77.2 mass % or less.

14. The polyethylene composition according to claim 1 or 2, wherein: In an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 98°C is 50 mass % or more and 70.0 mass % or less.

15. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1° C. by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50° C. to 94° C. was 11.2% by mass or more.

16. The polyethylene composition according to claim 1 or 2, wherein: In an elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1° C. by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50° C. to 94° C. is 12% by mass or more.

17. The polyethylene composition according to claim 1 or 2, wherein: The cumulative elution ratio from 50° C. to 94° C. is 14% by mass or more.

18. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 94°C was less than 38% by weight.

19. The polyethylene composition according to claim 1 or 2, wherein: In the elution temperature-cumulative elution amount curve obtained by measuring the elution amount per 1°C by temperature rising elution fractionation (TREF) using cross fractionation chromatography (CFC), the cumulative elution ratio from 50°C to 94°C was less than 34% by weight.

20. The polyethylene composition according to claim 1 or 2, wherein: Among the eluted components recovered at every 1°C by temperature rising elution fractionation (TREF) of cross fractionation chromatography (CFC), at least one weight average molecular weight (M w ) is an elution component of more than 250,000.

21. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition has a chlorine content of 31 mass ppm or less.

22. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition has a chlorine content of 21 mass ppm or less.

23. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition has a chlorine content of 20 mass ppm or less.

24. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains additives for imparting fluidity in an amount of 3,000 ppm by mass or less.

25. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains an additive for imparting fluidity in an amount of 50 ppm by mass or more and 4000 ppm by mass or less.

26. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains additives for imparting fluidity in an amount of 50 ppm by mass or more and 3000 ppm by mass or less.

27. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains additives for imparting fluidity in an amount of 100 ppm by mass or more and 4000 ppm by mass or less.

28. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains additives for imparting fluidity in an amount of 100 ppm by mass or more and 3000 ppm by mass or less.

29. The polyethylene composition according to claim 1 or 2, wherein: The polyethylene composition contains additives for imparting fluidity in an amount of 150 ppm by mass or more and 4000 ppm by mass or less.

30. The polyethylene composition of claim 1 or 2, wherein: The polyethylene composition contains additives for imparting fluidity in an amount of 150 ppm by mass or more and 3000 ppm by mass or less.

31. The polyethylene composition of claim 6, wherein: M1 / M2 is greater than or equal to 0.85 and less than or equal to 1.

15.

32. The polyethylene composition of claim 6, wherein: M1 / M2 is greater than or equal to 0.9 and less than or equal to 1.

1.

33. The polyethylene composition of claim 6, wherein: M3 / M2 is greater than or equal to 0.85 and less than or equal to 1.

15.

34. The polyethylene composition of claim 6, wherein: M3 / M2 is greater than or equal to 0.9 and less than or equal to 1.

1.

35. The polyethylene composition of claim 1 or 2, wherein: The difference between the resin temperature when the peak with the largest torque is detected and the resin temperature when the peak with the second largest torque is detected is 23° C. or less.

36. The polyethylene composition of claim 1 or 2, wherein: The difference between the resin temperature when the peak with the largest torque is detected and the resin temperature when the peak with the second largest torque is detected is 22° C. or less.

37. The polyethylene composition of claim 1 or 2, wherein: The difference between the resin temperature when the peak with the largest torque is detected and the resin temperature when the peak with the second largest torque is detected is 21° C. or less.

38. The polyethylene composition of claim 1 or 2, wherein: The difference between the resin temperature when the peak with the largest torque is detected and the resin temperature when the peak with the second largest torque is detected is 10° C. or more and 25° C. or less.

39. The polyethylene composition of claim 1 or 2, wherein: The polyethylene composition includes two or more polyethylene powders having different weight average molecular weights.

40. A method for producing a polyethylene composition according to any one of claims 1 to 39, wherein: The method comprises one or more of the following (1) to (4): (1) feeding the catalyst into the polymerizer from three locations, with one of the feed locations being adjacent to the ethylene feed location; (2) two catalyst feed positions away from the ethylene feed position are arranged near the liquid surface of the polymerizer, and the catalyst feed position close to the ethylene feed position is arranged near the bottom surface of the polymerizer; (3) No baffle is provided in the polymerizer; (4) Make the angle of the stirring blade of the polymerization reactor vertical.

41. The method for producing a polyethylene composition according to claim 40, wherein: The method further includes the following (5): (5) Delaying the deactivation of the catalyst in the flash tank by maintaining high temperature and low pressure conditions.

Citation Information

Patent Citations

  • PROCESS FOR THE PRODUCTION OF POLYOLEFINS AND THEIR COPOLYMERISATS

    DE3127133A1

  • Ultrahigh molecular weight polyethylene powder and method for producing the same

    JP2010235926A

  • Ethylene polymer and stretched molded body, microporous film and separator for battery

    JP2014118515A

  • Distribution estimation device, distribution estimation method, and distribution estimation program

    JP2017146829A

  • Ethylene polymer, tensile molded body, microporous membrane and diaphragm for battery

    CN103880993A